Temperature-fluctuation effects on shrimp protein quality assessed via a multi-stage temperature-fluctuation protein convolutional neural network - Zhexun Yang; Yiling Zhang; Sili Xiao; Weiteng Weng; Ziqi Xie; Jiayi Li; Wen Jie Li; Ying Deng; Yutao Wei; Yudan Li; Shuangyin Liu; Xuekai Gao; et al. (Journal of Food Engineering, 2027)

Seasonal dynamics of geogenic phosphorus in alluvial-lacustrine aquifers: Coupling of phosphorus-containing dissolved organic matter and microbes as a key driver - Junna Ning; Yao Du; Baisong Deng; Mengze Li; Tianming Wu; Lijie Lin; Taiping Yu; Yiqun Gan; Dandan Si; Wen Zhang; Yanxin Wang (Water Research, 2027)

Potato residue chips as corn replacement in Angus bulls: Effects on carcass characteristics, meat quality, and serum metabolites - Chang-Xiao Shi; Hui-Li Wang; Ying-Qi Li; Muhammad Aziz-ur-Rahman; Si-Yu Zhang; Jia-Jie Deng; Wen-Xi Zhao; Xing-Yue Yi; Yi-Min Zhang; Yang He; Bing-hai Cao; Hua-Wei Su (Food and Humanity, 2026)

Hierarchical transcription factor interaction network: RsrF mediates dual-layer regulation of plant-polysaccharide-degrading enzyme biosynthesis in fungus - Mei-Ling Pang; Wen-Tong Li; Ze-Yu Deng; Di Tian; Yan-Hao Zhao; Dian-Qi Wu; Xue-Mei Luo; Jia-Xun Feng; Shuai Zhao (Bioresource Technology, 2026)

A conditional generative diffusion model enables joint retrieval of rice LAI and LCC - Heguang Sun; Huanming Mai; Bo Han; Yi Zhang; Zhongyu Jin; Changsheng Li; Wenqian Tang; Zifan Shen; Ziheng Feng; Xiaoyu Song; Yubin Lan; Wen Du; et al. (Computers and Electronics in Agriculture, 2026)

An integrated gene annotation and body-wide single-cell atlas of the Pacific White shrimp, Litopenaeus vannamei - Xi Xiong; Zehua Zeng; Yuanyan Xiong; Weiwen Huang; Dandan Huang; Zhaojie Deng; Wen Li; Huiling Zhang; Zhiye Zeng; Hui Ren; Tianhong Chen; Lian Gan (Aquaculture, 2026)

A mitochondria-targeted fluorescent probe for monitoring of H2O2 and polarity/viscosity-related microenvironmental changes in food mycotoxin- and environmental contaminant-induced hepatotoxicity - Zibo Zhai; Jia Huang; Xijian Wang; Hailin Zhang; Min Deng; Qiqi Wen; Jingting Fang; Lizi Liu; Ziyang Ding; Dan Cheng; Longwei He; Songjiao Li (Journal of Environmental Chemical Engineering, 2026)

Lower crustal modification at the margin of the North China Craton: Multi-proxy geochemical and isotopic imaging constraints from the Late Mesozoic granitoids in Jiaodong Peninsula - Can-Can Wang; Li-Qiang Yang; Xue Gao; Wen-Yan He; Lei Ju; Dong Xie; Long Wang; Shi-Yao Zhai; Wei Yang; Nan Li; Zheng-Jiang Ding; Jun Deng (Journal of Asian Earth Sciences, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

Violet phosphorene: Recent advances from synthesis to advanced sensing applications - Yutang Wang; Liping Deng; Weiqiang Li; Yangping Wen (Chemical Engineering Journal, 2026)

Cooperative controlled release of ligands and metal ions for gram-scale growth of ultrathin 2D metal-organic frameworks - Li Yuan; Kuan Deng; Xuesong Liu; Yangzheng Bao; Ao Xia; Wen Tian; Junyi Ji (Chemical Engineering Journal, 2026)

Rosa roxburghii-derived Mg-doped carbon dots as bioactive nanoregulators in hydrogel scaffolds: orchestrating Nrf2/NF-κB signaling for enhanced periodontal repair in diabetes - Xuedong Deng; Lingxiang Sun; Xi Chen; Zheng Wang; Yilin Ping; Wen Ze Han; Lu Wang; Tingting Wu; Yifan Zhao; Bing Li; Xiuping Wu (Chemical Engineering Journal, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Dissolved inorganic phosphorus enrichment in groundwater of phosphate mining areas driven by multiple biogenic pathways - Junna Ning; Yao Du; Tianming Wu; Mengze Li; Baisong Deng; Wen Zhang; Yiqun Gan; Haomiao Yang; Xiaoxia Chen; Rui Ma; Yanxin Wang (Water Research, 2026)

Dietary Gamma-aminobutyric acid (GABA) in glucose and lipids metabolism: A review of biosynthesis, mechanisms, and functional food applications - Cong Chen; Sijie Zhang; Wen Deng; Ting Li; Xinxia Zhang; Cangliang Shen; Li Wang (Trends in Food Science & Technology, 2026)

Corynoxine suppresses hepatocellular carcinoma progression by forming the ROS-STAT3 cycle - Chunmei Wen; Mengyao Wang; Yitian Yu; Jiaxuan Mei; Yanju Ren; Qingqing Ruan; Jiale Xu; Jinxia Qi; Yangping Shentu; Jianmin Li; Jie Deng (Toxicology and Applied Pharmacology, 2026)

Sources and transport of potassium in a typical carbonate-type lake (Bangor Co) on the Qinghai-Tibet Plateau: Constraints from potassium isotopes - Jiangdi Zhou; Binkai Li; Jiangang Jiao; Maoyong He; Zhongli Tang; Yuanyuan Cheng; Zhengyan Li; Jiaxin Luo; Huihui Rao; Jing Wen; Li Deng; Zhikang Liu (Journal of Hydrology, 2026)

Simulation of pollutant transport and identification of longitudinal dispersion coefficient in vegetated channels based on a vegetation-constrained physics-informed neural network - Jiao Zhang; Suyuan Zhong; Wen Wang; Zhanbin Li; Peng Li; Jieyu Liu; Mengjing Guo; Lu Jia; Mingjiang Deng (Journal of Hydrology, 2026)

Unveiling the electrochemical reduction pathway of manganese release in drinking water distribution systems: A galvanic cell perspective on colored water risks - Tanyu Li; Dibo Liu; Luyao Kang; Jialiang Lan; Jun Wang; Gang Wen; Shuguang Xie; Lin Deng; Chao Chen (Journal of Hazardous Materials, 2026)

Study on “geometric deformation-multi-field coupling” model of coal spontaneous combustion and migration law of high temperature zone in dynamic fully-mechanized caving goaf - Yin Liu; Shijie Deng; Hu Wen; Lei Wang; Jun Guo; Changming Chen; Dailin Li (Fuel, 2026)

Modulating the crystal growth of manganese oxide via carbon fiber for efficient water purification with peroxyacetic acid oxidation - Rui Gan; Lijuan Huang; Rongling Wang; Yuxuan Ye; Qiang Li; Wen Liu; Yuwei Deng; Junxiong Cai; Fei Pan (Chemical Engineering Journal, 2026)

Lightweight Edge–Frequency Driven Real-Time Detection Transformer for side-scan sonar target detection - Feihu Zhang; Zhengpeng Li; Xin Wen; Chensheng Cheng; Biao Deng; Taiyuan Zhang; Guang Pan (Frontiers in Marine Science, 2026)
In underwater target detection tasks, side-scan sonar (SSS) is currently the most widely used imaging tool. However, due to the inherent imaging mechanism of sonar and the complexity of the underwater environment, SSS images often suffer from blurred target boundaries and strong noise interference, which significantly increases the difficulty of high-precision underwater target recognition. We propose a Lightweight Edge–Frequency Driven Real-Time Detection Transformer (LEF-RT-DETR) framework, aiming to improve both the detection accuracy and real-time performance for target detection in SSS images. Specifically, to address the distortion of target edge contours in SSS images, we design a Gaussian-Edge Enhancement Module (GEEM) by integrating Gaussian smoothing with edge extraction to enhance the model’s capability of perceiving target edge features. Simultaneously, to address severe noise interference in SSS images, we introduce the Multi-Scale Frequency-Spatial Denoising Block (MFDB), a feature fusion module integrating spatial-domain and frequency-domain information to improve the model’s ability to distinguish noise from targets. Finally, we propose the Partial Convolution with Efficient Channel Attention (PCCA), which reduces redundant channel computations and enhances inter-channel interactions via channel attention, thereby reducing model complexity while preserving high detection accuracy. Experimental results on a self-constructed dataset demonstrate that LEF-RT-DETR achieves improvements of 4.3% in Average Precision (AP) and 5.3% in Average Precision at an Intersection over Union (IoU) threshold of 0.50 (AP50) compared with the Real-Time Detection Transformer (RT-DETR), while reducing the number of parameters and computational cost by approximately 24% and 18%, respectively. This significantly enhances model accuracy and efficiency, providing robust support for real-time underwater target detection tasks.

A unified solution to the low-mass X-ray binary diversity puzzle: saturated magnetic braking coupled with irradiation-driven winds - Zhu-Ling Deng; Xiang-Dong Li; Bo Wang; Philipp Podsiadlowski; Yong Shao; Dong-Dong Liu; Zhan-Wen Han (Science Bulletin, 2026)

Corrigendum to “Simulation of pollutant transport and identification of longitudinal dispersion coefficient in vegetated channels based on a vegetation-constrained physics-informed neural network” [J. Hydrol. 677(Part B) (2026) 135849] - Jiao Zhang; Suyuan Zhong; Wen Wang; Zhanbin Li; Peng Li; Jieyu Liu; Mengjing Guo; Lu Jia; Mingjiang Deng (Journal of Hydrology, 2026)

Was the magma redox of the West Kunlun Paleo-Tethys modulated by surface environmental conditions of the Late Paleozoic Ice Age? - Zong-Yong Yang; Jing-Jing Zhu; Ruizhong Hu; Xian-Wu Bi; Li-Chuan Pan; Xing-Chun Zhang; Ju-Ting Deng; Yao-Wen Zhang; Qian Liu; Yi-Xin Li (Global and Planetary Change, 2026)

Separation of Value-Added chemicals from coal Tar: Mechanisms, Advances, and Perspectives - Pengzhi Bei; Jiayin Zhao; Xingtang Xu; Lan Yi; Lili Deng; Wen-Ying Li (Fuel, 2026)

Natural bioactive-loaded deep eutectic solvent-chitosan films as novel antioxidant packaging for color preservation in pre-prepared green peppers - Weiwei Gong; Haowei Lv; Linyan Deng; Boliang Li; Shiyi Lu; Haoran Fan; Yangyang Wen; Hongyan Li; Jing Wang (Food Research International, 2026)

Mg/Zn-coordinated solid–solid phase change material with intrinsic flame retardancy for battery thermal management - Qiqiu Huang; Xinxi Li; Peihui Chen; Hongli Liu; Chao Ren; Wen Luo; Ziyu Huang; Jian Deng; Wensheng Yang; Canbing Li; Yongliang Li (Chemical Engineering Journal, 2026)

GAC-YOLO: A Pomegranate Disease Rapid Detection Method with Multi-Scale Feature Enhancement for an Orchard Inspection Robot - Shenghui Fu; Yongchang Deng; Shuangxi Liu; Rongwei Li; Yuefeng Du; Linlin Sun; Hongjian Zhang; Tao Xu; Wen Zhang (Applied Fruit Science, 2026)

The real-world safety of ruxolitinib in graft-versus-host disease treatment: a pharmacovigilance study based on the FDA adverse event reporting system - Yuan-yuan Li; Wen-long Xie; Yang Zhao; Deng-zheng Zhang; Bing Mao; Qing Zhou; Yong-ji Lai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

GPD1-mediated neuronal lipotoxicity drives aconitine-induced mitochondrial collapse and lethality - Chen Jiang; Wen Hu; Sangyang Deng; Yongjie Huang; Linbo Wang; Zhenyu Yang; Yufei Li; Ping Li; Haiying Wu (Chemico-Biological Interactions, 2026)

A lightweight model RDMSegNet enabling UAV-Based high-resolution mapping of Sonneratia apetala for mangrove ecosystem ecological monitoring - Ziheng Zhang; Kai Liu; Wenwei Li; Jingjing Cao; Xin Wen; Chuying Yu; Haojian Deng; Zhe Xiang; Yuanhui Zhu (International Journal of Remote Sensing, 2026)

The eastern branch fault model of the Tanlu Fault zone and its controlling effect on hydrocarbon accumulation: A case study of southern section of Bohai Sea - Ji-mei Deng; Shi-qiang Xia; Wen-hui Huang; Peng Wu; Gang Han; Hong Li (Applied Geophysics, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Dinemasone D — a new polyketide derivative with anti-inflammatory activity from Phaeosphaeria poagena - Li-Bin Lin; Jia-Hao Ning; Kang-Hong Zhao; Jia-Yao Hu; Guang-Yu Bai; Pan Deng; Shao-Qi Tang; Wen-Ke Dou; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2026)

Pennsylvanian (Bashkirian) microbial reefs from Guizhou Province, South China: Characteristics and insights into the middle Carboniferous microbial reef development - Guan-Ming Lai; Yong-Li Zhang; En-Pu Gong; Ning-Feng Du; Wen-Tao Huang; Deng-Hui Chen; Yu Li; De-Peng Li (Palaeoworld, 2026)

Challenges in using platform carbonates to trace global seawater δ13C variations: A review and insights from terminal Ediacaran carbonate platforms - Yi Ding; Ya Zhang; Shugen Liu; Gang Zhou; Huaguo Wen; Daizhao Chen; Wei Yan; Caijun Lan; Yu He; Chao Deng; Zhiwu Li (Earth-Science Reviews, 2026)

Corrigendum to “Hellebrigenin induces cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells through inhibition of Akt” [Chemico. Biol. Interact. 219 (2014) 184-194] - Li-Juan Deng; Li-Ping Hu; Qun-Long Peng; Xiao-Lin Yang; Liang-Liang Bai; Anita Yiu; Yong Li; Hai-Yan Tian; Wen-Cai Ye; Dong-Mei Zhang (Chemico-Biological Interactions, 2026)

A LINE-1 retrotransposon promotes SEMA3C expression as a cis-regulatory enhancer to sustain breast cancer stem cell survival - Qidong Xia; Jingwei Feng; Jiayao Pan; Wen Deng; Xiaoqi Weng; Jianhui Jiang; Lin Wang; Wenqian Xie; Yi Chen; Aiwei Bi; Jiang Li; Yiwen Lu; et al. (Science China Life Sciences, 2026)

The “Last-mile Efforts” of Subseasonal Prediction and Services for Climate Resilience and Sustainability: Review and Outlook - Jing Yang; Mengqian Lu; Anling Liu; Tat Fan Cheng; Yuxian Pan; Miaoni Gao; Lun Dai; Shentong Li; Wen Deng; Xinyao Feng; Shiyu Zhang; Lu Tang; et al. (Advances in Atmospheric Sciences, 2026)
Subseasonal predictions from 2 weeks to 2 months have made significant advancements over the past decade, driven by progress in physical understanding, climate modeling, computational capabilities, and artificial intelligence (AI). These predictions are increasingly in demand due to their potential to provide stakeholders with adequate lead time for effective disaster adaptation, mitigation, and resource management. However, there remain critical gaps in the engagement between prediction providers and service users. Providers often lack insight into the specific needs of users and do not have transferrable strategies to build trust through tailored evaluations and clear confidence levels, which often results in repeatedly devising approaches for each provider–user interaction. Further, users frequently struggle to interpret predictions and are hesitant to make decisions based on these uncertain outcomes. This paper attempts to make “last-mile efforts” by reviewing relevant literature, operational systems, and the most informative communications and engagement strategies with key sectors. It proposes a preliminary framework to standardize the approach for provider–user interaction in the context of subseasonal prediction and services, with potential applicability and extension to seamless prediction systems in the future. Lastly, we underscore future directions for subseasonal predictions, emphasizing the integration of dynamic climate modeling and AI-driven enhancements with large ensemble techniques to improve both reliability and confidence. This review is part of the United Nations Educational Scientific and Cultural Organization (UNESCO) International Decade of Sciences for Sustainable Development (2024–33) and contributes to the Seamless Prediction and Services for Sustainable Natural and Built Environment (SEPRESS) Program (2025–32), an initiative endorsed under this global framework.

Dynamic and Static Biot’s Coefficient of Transversely Isotropic Longmaxi Shale - Lichun Jia; Hu Deng; Qicong Xu; Wen Xu; Lei Li; Luchun Li (Rock Mechanics and Rock Engineering, 2026)

Soil stoichiometric C/N and nitrogen availability jointly shape fungal and bacterial necromass carbon accumulation across ecosystems - Baorong Wang; Deng Ao; Chao Liang; Kate Buckeridge; Chunhui Liu; Yang Yang; Yao Li; Huijun Li; Zhongming Wen; Shaoshan An (Soil and Tillage Research, 2026)

Mechanistic insight into photodegradation of agricultural mulch films mediating the release micro(nano)plastic and dissolved organic matter to aquatic environments - Mengjie Wang; Huiming Yu; Jing Wei; Wenyi Xie; Xuwei Li; Lingya Kong; Ya Zhang; Tao Long; Qiong Wang; Shaopo Deng; Shixiang Gao; Wen-Tao Li (Chemical Engineering Journal, 2026)

Efficient ultraviolet emission via Ce3+-doped lead-free double perovskite nanocrystals for multicolor and full-spectrum luminescence - Zewen Wang; Xiaowei Deng; Xu Chen; Weilong Qin; Meng Wang; Yongjie Zai; Mochen Jia; Ying Liu; Zhuangzhuang Ma; Jibin Zhang; Linyuan Lian; Yanbing Han; et al. (Chemical Engineering Journal, 2026)

Photo-induced in-situ synthesized nanocellulose-based SERS substrate integrated with molecularly imprinted polymer for selective detection of pesticide residues - Xingyue Liu; Liucheng Meng; Wen Deng; Yuzhou Yang; Yanling Lou; Jianfeng Xi; Peng Li; Lei Zhang; Weibing Wu (Carbohydrate Polymers, 2026)

An Enzymatic Recombinase Amplification Coupled Lateral Flow Assay for Rapid, Visual, and Cost-Effective Detection of Bordetella pertussis - Piaoting Wen; Jian Liu; Mingqi Jiao; Hangxi Liu; Mei Lin; Sheping Zhang; Jun He; Ziyi Li; Changhui Xiao; Zhongliang Deng (Current Microbiology, 2026)

Food web modeling unveils ecological impacts of invasive species on an endemic fish (Anabarilius grahami) in an oligotrophic lake of southwest China - Suyan Deng; Wen Guo; Wenwen Wen; Linpei Huang; Guangjie Chen; Xu Wang; Zidong Chen; Li Chen (Biological Invasions, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Decoding volatile compound-aroma attribute correlations in representative Oolong Teas of Fujian: An integrated objective quantification and GC–MS profiling method - Chengzhe Zhou; Jiaxin Fang; Shuaibo Shao; Cheng Zhang; Caiyun Tian; Zhengdong Zhang; Anru Zheng; Yuting Li; Siwei Deng; Changlian Wu; Shengjing Wen; Nadang Long; et al. (Food Chemistry, 2026)

Umbilical Cord Mesenchymal Stem Cells and Wnt Pathway Modulation: A Novel Therapy for Liver Cirrhosis and Steatosis - Yanxuan Wen; Nouman Amjad; Omar Mukamab; Obed Boadi Amissah; Wei Xie; Peng Zhou; Aishi Song; Lan Wang; Jiaxing Li; Rongqi Huang; Sihao Deng; Zhiyuan Li (Tissue Engineering and Regenerative Medicine, 2026)

Evidence synthesis of soil effects from conservation measures on the Loess Plateau - Zemin Ai; Yuanyuan Zhang; Mingjiang Deng; Peng Li; Haoli Hu; Tian Cao; Xiaohu Dang; Wen Zhang; Li Li; Yaqi Nan (Plant and Soil, 2026)

miR-34c-3p promotes osteogenic differentiation of BMSCs by inhibiting DCBLD2 activation of the PI3K/AKT signaling pathway - Yongcheng Deng; Yihao Lei; Yi Ou; Junnan Li; Xingxi Hu; Lei Wen; Kaiyu Hou (Journal of Molecular Histology, 2026)

Endoscopic prediction model for detecting advanced rectal polyps after ileorectal anastomosis in familial adenomatous polyposis: a dual-center retrospective study - Zhilin Liu; Xingjie Gao; Shuling Chen; Linfu Zheng; Binbin Xu; Gaozhen Deng; Wen Wang; Kun Lin; Chushu Li; Zhou Ye; Dazhou Li (Familial Cancer, 2026)

Soil type regulates the development and insecticide susceptibility of Spodoptera frugiperda by modulating maize growth and nutritional content - Shi-Wen Deng; Mohammed Esmail Abdalla Elzaki; Wei Liang; Muhammad Hafeez; Wan-Ting Li; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2026)

New insights into divalent metal ions removal by sludge-derived porous carbon: Thermal evolution and synergistic adsorption at multi-active sites - Wenping Zhang; Shihao Zhang; Liang He; Yihao Li; Yong Wen; Zilian Liu; Rongrong Miao; Huajing Zhou; Xiaoyong Deng (Journal of Cleaner Production, 2026)

Multi-stage study of pyrolysis kinetics, combustion characteristics, and fire modeling for selected nature wood species - Yi-Xuan Lin; Qiang Wang; Qi-Xian Li; Qing-Wen Lin; Peng-Rui Man; Shu-Nan Zhou; Yang Li; Jun Deng (Fuel, 2026)

Natural sources and bioactive mechanisms of anti-inflammatory peptides: from digestive metabolism to bioavailability enhancement strategies - Shengbing Hu; Liwen Liang; Xinyi Peng; Wei Zhang; Wen Li; Jing Deng; Feifei Zhong; Qinlu Lin; Peng Zhou; Jintao He; Feijun Luo; Kilaza Samson Mwaikono (Food Chemistry, 2026)

Mechanistic insights into structural evolution of goji berry (Lycium barbarum L.) during pulsed vacuum drying procedure via moisture migration and cell wall polysaccharide transformations - An-An Zhang; Li-Zhen Deng; Long Xie; Ze-Kang Peng; Ming-Qiang Xu; Wan-Liang Hao; Yu-Hao Jiang; Wen-Bin Ze; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Deoxynivalenol induces testicular inflammation via mtDNA leakage-mediated activation of the cGAS-STING pathway in mice - Haihua Huo; Gaolong Zhong; Peixuan Li; Feiyang Chen; Yunpeng Deng; Lu Guan; Jiabin Chen; Yan Wang; Xu Wang; Qingmei Chen; Jikai Wen; Yiqun Deng; et al. (Food Bioscience, 2026)

Fermented Rhizoma Phragmitis alleviates alcoholic liver injury by coordinating hepatic metabolic homeostasis with the gut microbiota - Lidan Zhang; Wen Deng; Ming Zhang; Buyu Liu; Congnan Zhang; Ting Li; Xinxia Zhang; Juan Li; Li Wang (Food Bioscience, 2026)

Clostridium dalinum: A Novel Lactic Acid Bacterium with Excellent Antioxidant and Anti-inflammatory Functions Through NF-κB, Keap1-Nrf2-ARE Signaling Pathways - Zheng-Qiang Li; Rui Li; Wei Deng; Rui An; Ping Ma; Jun Li; Rong She; Xiao-Yan Yang; Xu Yang; Wen Xiao (Probiotics and Antimicrobial Proteins, 2026)

Magmatic control on the formation of the Diaoquan Ag-(Cu-Au) skarn deposit in the eastern North China Craton as revealed by zircon, apatite and sulfides - Gao-Hua Fan; Jian-Wei Li; Paul T. Robinson; Kai-Xuan Hui; Xiao-Dong Deng; Wen-Sheng Gao; Jin-Hao Liu; Hang-Jin Jiang (Mineralium Deposita, 2026)

Hydrogeophysical Imaging and Joint Interpretation of Rainfall Infiltration on an Embanked Slope in the Mid-Lower Yangtze Hilly Region - Rong-wen Guo; Chen-yang Li; Zhuo Liu; Deng-kang Wang; Ming Yu (Applied Geophysics, 2026)

Research on real time mapping and transfer learning based 3D semantic segmentation of unstructured orchards - Sipei Li; Sheng Wen; Fagang Liu; Haiyan Zhang; Yufeng Ge; Zhiyin Deng (Computers and Electronics in Agriculture, 2026)

Synergistic virulence of H9N2 AIV and APEC co-infection in laying hens involves a critical role for macrophage-mediated hyper-inflammation via the MAPK/NF-κB axis - Jinjie Han; Wenchi Chang; Zhaoyue Jing; Dong Xiao; Tiantian Ji; Junyang Fang; Mengzhao Song; Wei Li; Jingyu Wang; Wen Deng (Veterinary Microbiology, 2026)

A solo-LTR insertion in the CreTPS3a promoter enhances γ-terpinene biosynthesis and affects consumer preference for tangerine-like aroma in citrus fruits - Huan Wen; Yuan Liu; Zhehui Hu; Dongxuan Wu; Lingling Shui; Zhipeng Zhao; Gu Li; Guixiang Chen; Jiajing Chen; Xiao Liu; Xiaolin Chen; Cecilia Hong Deng; et al. (Molecular Plant, 2026)

Determining the source contributions of dissolved organophosphorus compounds in lake water utilizing FT-ICR-MS and PCA-APCS-MLR receptor models - Xinrui Jiang; Yao Du; Mengze Li; Rui Xu; Tianming Wu; Baisong Deng; Dandan Si; Wen Zhang; Jingwen Yu; Yanxin Wang (Journal of Hydrology, 2026)

A multi-objective optimization framework for check dam siting integrating GIS, a hydrological–hydrodynamic coupling model, and NSGA-II - Minghao Deng; Zhanbin Li; Wen Wang; Jiao Zhang; Ke Xiang; Yunxian Wang (Journal of Hydrology, 2026)

Experimental and numerical study on oxygen-enriched NH3/H2/CO/air premixed combustion at elevated temperature and pressure - Ningning Li; Haoxin Deng; Xiaoping Wen; Fahui Wang; Jun Song; Guoyan Chen (Journal of Cleaner Production, 2026)

Food-derived antioxidant peptides mediated multifunctional bioactivities and bioavailability-enhancing delivery strategies via the Nrf2/Keap1 signaling pathway - Wei Zhang; Shengbing Hu; Haiyan Tang; FeiFei Zhong; QinLu Lin; Wen Li; Jing Deng (Food Chemistry, 2026)

Face-off: Shark or pork? DNA barcoding authentication and labelling analysis of shark products (intestine and stomach) available on Chinese e-commerce - Xia Zhang; Lara Tinacci; Alice Giusti; Huiru Kang; Sihui Li; Weide Deng; Yuan Li; Zhenzhu Sun; Hongyuan Peng; Lu Zou; Xinjie Li; Andrea Armani; et al. (Food Control, 2026)

Design of active ester curing agent containing imide and fluorine for plant oil-based epoxy resins with high Tg and low dielectric constant - Jing Li; Maoping Lyu; Junjie Wen; Henghui Deng; Ying Luo; Zehong Chen; Chaoqun Zhang (Chemical Engineering Journal, 2026)

Structural characterisation of a novel polysaccharide from pseudostellaria heterophylla fibrous root and its anti-inflammatory and antioxidant activities in vitro - Meng-Yu Li; Hai-Tian Deng; Ming-Zhu Ye; Li-Li Lu; Hong-Yuan Chen; Wen Rui (Natural Product Research, 2026)

Fatal infection of a novel canine/human reassortant H3N2 influenza A virus in the zoo-housed golden monkeys - Xia Wen; Rong Chen; Yingjun Lv; Jinzhu Geng; Jingjing Guo; Yaru Sun; Aohan Yang; Yuhao Dong; Meirong Li; Changlin Deng; Guodong Wang; Yongjie Liu (Veterinary Microbiology, 2026)

Cytochalasans from the fungus Chaetomium globosum with cytotoxic activities against HepG2 cell line - Hong-Fei Li; Tian Jin; Jiao-Xian Du; Xin-Wen Luo; Guo Zhang; Wang-Qiu Deng; Juan He; Tao Feng (Phytochemistry, 2026)

Chronic nanoplastics exposure drives lung cancer progression through ATF3/PCK2 axis-mediated rewiring of truncated gluconeogenesis - Qian Li; Wenwen Meng; Chengting Xie; Fei Wang; Yating Deng; Keying Chen; Yi Li; Yuqiao Li; Yixian Wen; Jing Zhu; Tingli Han; Xuemei Chen; et al. (Journal of Hazardous Materials, 2026)

Three-dimensional shear-wave velocity structure of the longnan geothermal field in the Central Jiulianshan uplift derived from seismic ambient noise tomography - Ronghua Xu; Juzhi Deng; Cheng Li; Huajian Yao; Yang Gao; Zequn Wen (Journal of Applied Geophysics, 2026)

Promoting aerobic denitrification in the rhizosphere by vertical spatial stress: A strategy to enhance nitrogen conversion efficiency in constructed wetlands - Sheng-Jing Zhang; Hao-Qi Lu; Lei Yang; Li-De Wang; Bi-Han Zhang; Chao-Wen Deng; Jun Lan; Yong-Xiang Ren (Environmental Research, 2026)

Source-driven stratified accumulation and health exposure of VOCs and PFAS in underground commercial complexes - Liyuan Zhang; Yuhang Ding; Pengyue Zhu; Jiangwei Li; Yuqi Wang; Wei Zhong; Wen Fan; Longsheng Deng; Yue Zhang (Building and Environment, 2026)

Evaluating quasi-elastic behavior in granular Materials: Insights from cyclic loading tests - Pingxin Xia; Qingqing Fu; Wen Deng; Xiaoshuang Li; Maosen Han; Tiande Wen (Soil Dynamics and Earthquake Engineering, 2025)

Synergistic heating and electrokinetic effects of direct current electric fields: numerical modeling of multi-field coupling for contaminant removal in heterogeneous porous media - Qianli Xie; Di Zheng; Zhuning Geng; Jia Deng; Zhang Wen; Guanghe Li; Fang Zhang (Journal of Hydrology, 2025)

Amoxicillin effects on pollutant removal, cyanophycin synthesis, and the proliferation of antibiotic resistance genes (ARGs) in the algal-bacterial biofilm - Miaomiao Wen; Chuyun Deng; Jiawei Lei; Xueqi Yang; Jiahao Li; Naif Abdullah Al-Dhabi; Shulong Wen; Wangwang Tang; Bo Feng; Peng Zhang (Journal of Hazardous Materials, 2025)

Characterizing the impact of lactic acid bacteria-fermented vegetable juice on microbial assemblage and quality of pickled suancai - Kaidi Hu; Jing Li; Min Zhang; Yizhuo Wan; Yankang Yang; Jingyi Ren; Zerong Jin; Wen Wang; Yunxiao Wan; Qisheng Zhang; Dongdong Wang; Weiqin Deng; et al. (Food Research International, 2025)

Octacosanol: Biological activities and bioavailability enhancement strategies - Liwen Liang; Xin yi Peng; Qiong Xiao; Feifei Zhong; Xiaoxi Zeng; Wen Li; Jing Deng; Qinlu Lin; Feijun Luo; Qingming Cao; Kilaza Samson Mwaikono (Food Chemistry, 2025)

A dual-functional antifungal and anti-Drosophila polylactic acid nanofibers film loaded with Litsea cubeba essential oil/β-cyclodextrin inclusion complex for Chinese bayberry preservation - JinTao He; MingXuan Zhu; ChengHao Yang; Wen Li; Jing Deng; QinLu Lin (Food Chemistry, 2025)

Systematic profiling and bioactivity evaluation of Jiuzao from light flavor baijiu: A by-product rich in bioactive compounds - Siqi Hu; Yuting Zeng; Hongqin Liu; Mingquan Huang; Hui Li; Wen wen Deng; Jihong Wu; Hehe Li; Xiaotao Sun (Food Chemistry, 2025)

Effect of salt stress-induced germination technology on the phenolic composition, antioxidant capacity, and metabolic pathways of highland barley (Hordeum vulgare L.): A metabolomics insight - Shuyao Wen; Disheng Xiao; Linlin Ye; Shimin Liu; Miao Liu; Xiaoyi Hou; Hui Li; Na Deng; Jianhui Wang (Food Bioscience, 2025)

A review on migration behavior and safety regulation of inorganic nanoparticles in food packaging: Multi-scale mechanisms, risk assessment, and innovative strategies - Jingjing Wang; Xu Liang; Huanhuan Hou; Jing Deng; Qinlu Lin; Wen Li; Jie Bai (Food Control, 2025)

Heterogeneity analysis and prognostic model construction of HPV negative oral squamous cell carcinoma T cells using ScRNA-seq and bulk-RNA analysis - Chunyan Li; Zengbo Lv; Chongxin Li; Shixuan Yang; Feineng Liu; Tengfei Zhang; Lin Wang; Wen Zhang; Ruoyu Deng; Guoyu Xu; Huan Luo; Yinhong Zhao; et al. (Functional & Integrative Genomics, 2025)

Genesis of the Pulang polymetallic mineralization system in Yunnan Province, China: Insights from in situ trace element and S isotope analyses of pyrite - Xiao-Yu Zhao; Zi-Chao Tang; Ming-Guo Deng; Wen-Chang Li; Jing-Wei Xu; Yan Su; Zhi-Peng Li; Lei Wang (Journal of Geochemical Exploration, 2025)

Interaction mechanism and structure-activity relationship of hesperidin, methyl hesperidin and hesperidin methyl chalcone with ovalbumin: A comparative study - Xuefei Wen; Xinpeng Li; Siming Zhu; Liang Chen; Zhendong Wang; Ming Yu; Zhanhua Deng (Food Chemistry, 2025)

The multimodal anti-tumor effect of cisplatin nanoparticles loaded with bacterial antibodies in combination with radiotherapy: targeting hypoxic tumor and reshaping of the immune microenvironment - Min Wu; Zhouxue Wu; Weizhou Wang; Yunxue Zheng; Hongxia Li; Yuan Huang; Liping Deng; Yingqi Gu; Jinfeng Rong; Xiaoyin Zhang; Wen Yang; Yue Chen; et al. (Chemical Engineering Journal, 2025)

In situ multiplexed imaging of miRNA heterogeneity in single urinary exosome enables non-invasive bladder cancer diagnosis - Yang Wang; Huaxing Li; Xiangqian Cao; Weiguang Zhao; Hongquan Gou; Chenkai Yang; Haoyuan Wang; Jie Deng; Wen Chen; Haipeng Qi; Dongsheng Mao; Xiaoli Zhu; et al. (Chemical Engineering Journal, 2025)

Heavy metal exposure and cognitive impairment: An umbrella review of meta-analyses - Yueqing Song; Yantong Chen; Zhushan Fu; Yi Wen; Weiyue Zhao; Jia Li; Haocheng Wang; Yinke Du; Yu Deng (Journal of Hazardous Materials, 2025)

Combined scale inhibition of modified polyepoxysuccinic acid and electrochemical water softening - Xuesong Chen; Lida Wang; Hejin Li; Zhongqiang Yu; Wen Sun; Zhengqing Yang; Haitao Deng; Qian Wang; Junhai Luo; Guichang Liu (Journal of Environmental Chemical Engineering, 2025)

Freeze-thaw and dry-wet alternation regulate the impacts of Fe-C based passivator on soil heavy metals immobilization - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Shan Li; Wen Ni; Siqi Zhang (Journal of Environmental Chemical Engineering, 2025)

Chalcophile elements in post-subduction magmas and implications for metal recycling in oceanic and continental subduction - Xiang Wang; Zaicong Wang; Li-Qun Dai; Wen Zhang; Xiaodong Deng; Xi Zhang; Stephen Foley; Charles H. Langmuir; Wei Fang; Lang Wang; Tao He; Aiqing Ren; et al. (Geochimica et Cosmochimica Acta, 2025)

The role of potassium in lode gold mineralization: insights from ab initio molecular dynamics and geochemical modeling - Gao-Hua Fan; Jian-Wei Li; Yuan Mei; Si-Yu Hu; Ri-Chen Zhong; Chang Yu; Xiao-Dong Deng; Hao Cui; Wen-Sheng Gao (Geochimica et Cosmochimica Acta, 2025)

Beyond mislabelling: Chinese fish balls authentication by metabarcoding allows unveiling hidden mammal and avian species - Xia Zhang; Alice Giusti; Sihui Li; Weide Deng; Zhenzhu Sun; Yuan Li; Hongyuan Peng; Jiajie Hu; Andrea Armani; Jing Wen (Food Control, 2025)

Associations of urinary biomarkers of exposure to drinking-water disinfection by-products with haematological parameters and systemic inflammation indices among women undergoing assisted reproductive technology treatment - A-Xue Liu; Yu Miao; Min Zhang; Xiao-Ying Liu; Yan-Ling Deng; Jia-Yue Zeng; Yang-Juan Li; Wen-Qing Lu; Chang-Jiang Liu; Qiang Zeng (Environmental Pollution, 2025)

Integrative Analysis of the Microbiome and Metabolome of Broiler Intestine: Insights into the Mechanisms of Probiotic Action as an Antibiotic Substitute - Yang Li; Jian-Ling Zhang; Jia-Qi Chen; Zhuang Chen; Shi Liu; Jing Liu; Wen-Jie Huang; Jia-Zhou Li; Dong Ruan; Jun-Jin Deng; Zhi-Lin Wang (Probiotics and Antimicrobial Proteins, 2025)

Microbial transformation of geniposide in Gardeniae Fructus under the fermentation with Aspergillus niger DQWM-G11 - Xiao-Xin Xu; Xue-Jiao Li; Ke-Wen Pan; Liang Deng; Shu-Biao Xia; Jian-Wei Dong (Natural Product Research, 2025)

Development and evaluation of a novel sensor for noninvasively investigating corn ear dehydration - Yang Xiang; Liu-Deng Zhang; Hai-Ying Zheng; Ao-Wen Wang; Ke-Lei Xia; Zhong-Yi Wang; Lan Huang; Li-Feng Fan (Computers and Electronics in Agriculture, 2025)

Bimetallic catalyst with dual-reaction-center and oxygen vacancies for synergistically boosting peracetic acid activation and decontamination via 1O2 generation - Shuo Li; Yalun Yang; Heshan Zheng; Junfeng Niu; Ying Deng; Jun Ma; Yoong Kit Leong; Jo-Shu Chang; Wen-Wei Li (Water Research, 2025)

Transcriptional factors AcNAC1/2 synergistically orchestrate kiwifruit chlorophyll degradation - Ying-ying Wu; Shi Wu; Xin-yi Li; Jia-hui Deng; Pu Liu; Wen-qiu Wang; Xue-ren Yin; Xiao-fen Liu (Postharvest Biology and Technology, 2025)

Mechanism of 5-hydroxymethylfurfural on renal lipid metabolism based on endoplasmic reticulum stress - Xinyi Zhou; Fajian Ren; Hua Deng; Yan Huang; Ziyi Li; Jiayu Wen; Qiwen Xiang; Minggui Ha; Tian Leng; Chaolong Rao (Food Bioscience, 2025)

Versatile defect-laden boronizing hard carbon for superior sodium-ion battery efficacy - Jiayi Wen; Cheng Liu; Mingjun Jing; Dan Li; Honghui Hu; Huaxin Liu; Tianjing Wu; Lanhua Yi; Yong Pei; Xue Zhong; Wentao Deng; Guoqiang Zou; et al. (Chemical Engineering Journal, 2025)

Super-adhesive and highly sensitive conductive hydrogel based on halometallate ionic liquid for flexible electronic devices - Wen Li; Fang Wang; Jiaqi Liu; Jiajun Wang; Lingqi Deng (Chemical Engineering Journal, 2025)

A synergetic surface and bulk modification of 4.6 V LiCoO2 through nickel oxalate incorporated solid reaction synthesis - Lei Xu; Yajun Zhao; Sichen Jiao; Hongyi Pan; Jiacheng Zhu; Chengzhen Zhang; Penghao Chen; Kun Zhou; Bowei Cao; Yapei Li; Biao Deng; Juping Xu; et al. (Chemical Engineering Journal, 2025)

Modification effects of socioeconomic, demographic, and geographic factors on the association between temperature and cause-specific mental disorders among Taiwanese population - Gerry Andhikaputra; Li-Wen Deng; Hsi-Yu Hsiao; Yu-Kai Lin; Ta-Chien Chan; Hsuan-Fu Chao; Yu-Chun Wang (International Journal of Biometeorology, 2025)

Occurrence, Distribution, Sources, and Risk Assessment of Heavy Metals in Brownfields From Wuhan, Central China - Yu Huang; Yue Xing; Yifei Leng; Bo Deng; Wenbo Yuan; Xiaotian Du; Wei Wang; Kunpeng Li; Wen Xiong (Bulletin of Environmental Contamination and Toxicology, 2025)

Responses of multi-trophic microbial communities to altered precipitation affected soil respiration in coastal wetlands - Yuqi Zhou; Xinge Li; Shuzhen Li; Xiongfeng Du; Zheng Zhang; Zhaojing Zhang; Kai Feng; Xi Peng; Wen Song; Song Gu; Pengpeng Duan; Baohua Xie; et al. (Applied Soil Ecology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

The microhabitat regulation of moisture - ventilation mediated microbial carbon metabolism in response to humic acid formation during chicken manure and food waste composting - Liqin Wang; Xinzi Wen; Yu Deng; Zimin Wei; Jie Li; Caihong Song (Journal of Environmental Management, 2025)

Two magmatic-hydrothermal events in Xinzhai Sn polymetallic deposit, Yunnan Province, China: Constraints from cassiterite U-Pb geochronology and elemental compositions of single fluid inclusions - Ying-Hua Chen; Wen-Chang Li; Ting-Guang Lan; Xiao-Yu Zhao; Ming-Guo Deng; Die Wang; Yan-Wen Tang; Ji-Huang Lai (Gondwana Research, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

RNFT2 promotes malignancy of triple-negative breast cancer and predicts poor outcomes - Shi Tang; Peiqi Wen; Yuanyuan Chen; Kaiheng Li; Jiehua Deng; Jinghui Chen; Lianghai Lai (Journal of Molecular Histology, 2025)

Flavobacterium aestuarii sp. nov., a novel species isolated from the Pearl River Estuary - Qi Li; Zi-Qi Peng; Hong-Chuan Wang; Lei Dong; Dan-Yuan Guo; Pan-Deng Wang; Xiao-Qing Luo; Zhen-Hao Luo; Zi-Wen Yang; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Effects of early-life air pollution exposure on childhood COVID-19 infection and sequelae in China - Chan Lu; Wen Deng; Zipeng Qiao; Wenying Sun; Wanxue Xu; Ting Li; Faming Wang (Journal of Hazardous Materials, 2025)

Assessing the growth dynamics of Listeria monocytogenes and microbiota in RTE poultry: A combined BP-ANN and traditional approach - Zichen Deng; Wenqian Li; Yihuan Song; Hongyi Wen; Yongxian Zhang; Yan Du; Yan Wang; Can Huang; Jingyu Chen (International Journal of Food Microbiology, 2025)

Effects of combustion promoters in a narrow-gap disk ammonia/air premixed combustion system: Flame propagation and reaction kinetic analysis - Shoutong Diao; Haitao Li; Xiaoping Wen; Minggao Yu; Zhidong Guo; Chengcai Wei; Haoxin Deng (Fuel, 2025)

Variations in 3-chloropropanol esters, glycidyl esters, and lipid accompaniments during the simulated moderate decolorization process of maize germ oil - Yu Jie Wang; Li Li Xu; Ai Zhen Zong; Fang Ling Du; Deng Yu Xie; Yun Qi Wen; Tong Cheng Xu (Food Chemistry, 2025)

Enabling fast-charging capability of high-voltage solid-state lithium metal batteries by in-situ composite of COF into polymer electrolyte - Jiazhu Guan; Xintian Li; Luqi Zhou; Qinghui Zeng; Yu Liu; Honghao Wang; Yuchen Jiang; Zhenfeng Li; Lin Chen; Yong Cao; Rongzheng Li; Wen Wen; et al. (Chemical Engineering Journal, 2025)

Combined Zinc and Metformin Attenuated Impairment of Corpus Cavernosum Function, Imbalance of Zinc Homeostasis, Apoptosis, and Fibrosis in STZ-Induced Diabetic Mice by Inhibiting the TGF-β1/Smad3 Pathway - Huanhuan Li; Zongkai Wu; Jiaoying Ma; Wen Li; Peipei Deng; Shusong Wang; Jing Ma (Biological Trace Element Research, 2025)

Transcription factor FOXD3 participates in the immune response of Pinctada fucata martensii by regulating nAChR-5 - Min Yang; Yongge Huang; Xinyi Lin; Zhihan Li; Shilin Zheng; Youmei Qu; Yue Wen Deng; Ronglian Huang; Yu Jiao (Aquaculture, 2025)

Characterization of the thioredoxin peroxidase gene and its role in lambda-cyhalothrin tolerance in Agrotis ipsilon (Lepidoptera: Noctuidae) - Yu Gao; Dong-Yang Liu; Quan Deng; Wen-Long Feng; Jia-Min Yu; Mao-Ye Li; Su Liu (Journal of Asia-Pacific Entomology, 2025)

Effect and mechanism of calcium ions on the astringency in green tea infusion and epigallocatechin gallate solution: An in vitro oral soft tribology study - Long-Jie Xu; Qing-Qing Cao; Si-Han Deng; Wen-Jiang Dong; Qian Zou; Yong-Quan Xu; Xing-Hui Li (Food Chemistry, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Application of scattering image wavelet transform in cave recognition: A case study on a bedrock buried hill reservoir in Bongor Basin, Chad - Yu-Jiang Xiao; Tao Song; Li-Deng Gan; Yan Zhang; Wen-Hui Du; Xing-Yan Fan; Xiao-Feng Dai (Applied Geophysics, 2025)

A 10-Year Dataset of Land Surface Observations for the Semi-Humid Alpine Grassland in the Source Region of the Yellow River - Xianhong Meng; Yu Zhang; Lunyu Shang; Shaoying Wang; Zhaoguo Li; Shihua Lyu; Yinhuan Ao; Siqiong Luo; Lijuan Wen; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2025)
The source region of the Yellow River, accounting for over 38% of its total runoff, is a critical catchment area, primarily characterized by alpine grasslands. In 2005, the Maqu land surface processes observational site was established to monitor climate, land surface dynamics, and hydrological variability in this region. Over a 10-year period (2010–19), an extensive observational dataset was compiled, now available to the scientific community. This dataset includes comprehensive details on site characteristics, instrumentation, and data processing methods, covering meteorological and radiative fluxes, energy exchanges, soil moisture dynamics, and heat transfer properties. The dataset is particularly valuable for researchers studying land surface processes, land–atmosphere interactions, and climate modeling, and may also benefit ecological, hydrological, and water resource studies. The report ends with a discussion on perspectives and challenges of continued observational monitoring in this region, focusing on issues such as cryosphere influences, complex topography, and ecological changes like the encroachment of weeds and scrubland.

Triploidy induction through cntd1 knockout in red crucian carp (Carassius auratus red var.) - Huilin Li; Yu Zhang; Lina Zhang; Juan Li; Yuan Ou; Ming Wen; Zehong Wei; Jing Wang; Yu Deng; Yinjun Jiang; Conghui Yang; Yuqin Shu; et al. (Aquaculture, 2025)

Polymetallic Te-rich melts contribute to efficient enrichment and precipitation of Au in hydrothermal ore deposits - Gao-Hua Fan; Jian-Wei Li; Ri-Chen Zhong; Sarah A. Gleeson; Zhuo-Sen Yao; Daniel E. Harlov; Xiao-Dong Deng; Hao Cui; Chang Yu; Wen-Sheng Gao (Geochimica et Cosmochimica Acta, 2025)

Tough, antibacterial, and antioxidant chitosan-based composite films enhanced with proanthocyanidin and carvacrol essential oil for fruit preservation - Lijun Qian; Ruijing Jia; Quanling Zhao; Ningjing Sun; Juan Yang; Jialong Wen; Han Li; Jisheng Yang; Liuting Mo; Wei Gao; Shuduan Deng; Zhiyong Qin (Food Research International, 2025)

Differentiation of Citri Reticulatae Pericarpium varieties via HPLC fingerprinting of polysaccharides combined with machine learning - Min-yong Zhong; Meng-ning Li; Wen-shu Zou; Si-qi Hu; Jiang-nan Luo; Qing-xiang Jiang; Qiu-fang Cao; Long-fei Lin; Zhi-xin Wang; Hui Li; Wen-wen Deng (Food Chemistry, 2025)

Enhancement of Oryzanol application by constructing modified β-CD inclusion complex and polycaprolactone-chitosan electrospun fiber membranes: Perspectives on wound dressings and grape preservation - Wen Li; Jintao He; Qijue Chen; Feng Bao; Yinqiang Huo; Jing Deng; Qinlu Lin; Feijun Luo (Food Chemistry, 2025)

Orthogonal DNA self-assembly technology enables rapid and accurate analysis of circulating tumor cells in breast cancer - Min Li; Runchi Zhang; Xiaozhi Huang; Meng Jian; Haipeng Qi; Xiaolong Chen; Jie Deng; Wen Chen; Chang Feng; Qiongzhu Dong; Bin Su (Analytica Chimica Acta, 2025)

A multi-satellite survey scheme for addressing open questions on the Earth’s outer radiation belt dynamics - Xiaochao Yang; Xinlin Li; Lei Dai; Ji Wu; Vladimir Kalegaev; Wen Li; Yoshizumi Miyoshi; Wenlong Liu; Zheng Xiang; Binbin Ni; Si Liu; Daniel N. Baker; et al. (Advances in Space Research, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Failure Characteristics and Control Strategies of Overlying Remaining Coal Pillars in Close-Distance Coal Seam Mining - Wei-guang Ren; Hui Yuan; Zhi-gang Deng; Yun-peng Li; Wen-xin Li (Applied Geophysics, 2025)

Purification of Intensive Shrimp Farming Effluent by Gracilaria Coupled with Oysters - Junjing Li; Yu Xu; Yunlong Deng; Xiaojuan Hu; Haochang Su; Guoliang Wen; Yucheng Cao (Fishes, 2025)
In this study, we explored the ability of Gracilaria vermiculophylla coupled with Crassostrea hongkongensis to purify aquaculture effluent by analysing the purification of intensive shrimp farming effluent using G. vermiculophylla under different environmental conditions. After determining the optimal conditions, we further investigated the capability of the G. vermiculophylla and oyster coupling in intensive shrimp farming effluent purification. The shrimp farming density was 200 individuals per cubic metre (equivalent to 0.2 individuals per litre). The optimal environmental parameters were as follows: oyster biomass of 4.5 kg·m−3, G. vermiculophylla biomass of 2 kg·m−3, water temperature of 25–30 °C, and salinity of 15–30‰; the total inorganic nitrogen, PO43−-P, total nitrogen, and total phosphorus removal rates were 59.56%, 97.43%, 63.67%, and 76.25%, respectively, with G. vermiculophylla increasing in weight by 31.01%. For every 1 kg increase in the dry weight of G. vermiculophylla, 36.89 g of N and 12.40 g of P could be absorbed from the effluent. Our findings indicate that the coupling of G. vermiculophylla with oysters greatly contributed to the purification of effluent from intensive shrimp farming and can, thus, be used for treating intensive shrimp farming effluent.

Tumor cell-derived N-acetyl-aspartyl-glutamate reshapes the tumor microenvironment to facilitate breast cancer metastasis - Jie Xia; Lixing Zhang; Wucheng Zhu; Juchuanli Tu; Xilei Peng; Qiaodan Deng; Siqin Li; Xueyan He; Haonan Dong; Cuicui Liu; Xian Chen; Jiahui Xu; et al. (Science Bulletin, 2025)

An intelligent thymol/alizarin-loaded polycaprolactone/gelatin/zein nanofibrous film with pH-responsive and antibacterial properties for shrimp freshness monitoring and preservation - JinTao He; Qiong Peng; JingJing Wang; Jing Deng; Wen Li; QinLu Lin; FeiFei Zhong; Xu Xia (Food Chemistry, 2025)

Dek570-1, a PPR-DYW protein, is required for maize seed and plant development via modulation of C-to-U RNA editing in mitochondria and chloroplasts - Wenjie Li; Mengsha Zhao; Baiyu Liu; Yecan Liu; Jiaying Deng; Yu Gu; Min Liu; Wen Cheng; Zhaohua Ding; Kunpeng Li (Planta, 2025)

Single-cell atlas profiling revealed cellular characteristics and dynamic changes after PD-1 blockade therapy of brain metastases from laryngeal squamous cell carcinoma - Yunzhi Zou; Hao Duan; Zekun Deng; Rong Xiang; Jixiang Zhao; Zhenhua Zhang; Wanming Hu; Yuanzhong Yang; Zeming Yan; Shujuan Wen; Zexian Liu; Gao Zhang; et al. (Molecular and Cellular Biochemistry, 2025)
Brain metastasis (BM) in laryngeal squamous cell carcinoma (LSCC) is uncommon but prognosis is poor. Anti-PD-1 immunotherapy benefits some advanced LSCC cases, yet its efficiency is limited by tumor complexity. We analyzed paired metastatic tumor samples from before and after immunotherapy using single-cell RNA sequencing (scRNA-seq), along with a primary LSCC dataset and bulk RNA sequencing. This identified changes post-immunotherapy and revealed differences in single-cell transcriptomes among LSCC, primBM, and neoBM. Our findings show that anti-PD-1 treatment suppresses metastasis-promoting pathways like VEGF and EMT in cancer cells, and alters immune cell functions. Notably, it upregulates T cell activation, leading to CD8 T cell exhaustion from excess heat shock proteins, notably HSPA8. However, CD8 T cell cytotoxic functions improve post-treatment. In myeloid cells, anti-PD-1 therapy enhances antigen presentation and promotes a proinflammatory shift post-metastasis. Additionally, NUPR1 is linked to BM in LSCC, and NEAT1 is a potential metastatic cancer cell cycle participant. Our study provides insights into cancer heterogeneity and the impact of PD-1 immunotherapy on metastasis, aiding precise diagnosis and prognosis.

Targets and Potential Mechanism of Chondroitin Sulfate A-selenium Nanoparticle on Kashin-Beck Disease Chondrocytes - Huan Deng; Feidan Deng; Xinyue Wen; Yude Jiang; Abebe Feyissa Amhare; Lichun Qiao; Miaoqian Li; Ping Wan; Jun Wang; Jing Han (Biological Trace Element Research, 2025)

EDC3 protein of P-body suppresses PRRSV proliferation and functions by upregulating MyD88 - Yiran Wang; Changhong Li; Qiaomu Deng; Xuan Hu; Jing Zhao; Hongxing Yang; Guilan Wen (Veterinary Microbiology, 2025)

Targeted isolation of lignans and triterpenoids from kadsura coccinea by molecular networking and anti-RA-FLS activity - Shi-qi Liu; Qing-ling Xie; Ya-si Deng; Ling Liang; Han-wen Yuan; Bin Li; Huang-he Yu; Xing Tian; Yi-xing Qiu; Guy Paulin Kemayou Mouthe; Nuzhat Shehla; Ye Zhang; et al. (Phytochemistry, 2025)

A chemically enhanced primary treatment and anammox-based process for sustainable municipal wastewater treatment: The advantage and application prospects - Ruolan Wen; Jiayuan Deng; Huan Yang; Yu-You Li; Hui Cheng; Jianyong Liu (Journal of Environmental Management, 2025)

Impact of meteorological uncertainties on PM2.5 forecast: An ensemble air quality forecast study during 2022 Beijing Winter Olympics - Wei Wen; Liyao Shen; Li Sheng; Xin Ma; Jikang Wang; Chenggong Guan; Guo Deng; Hongqi Li; Bin Zhou (Atmospheric Environment, 2025)

KCNJ15 inhibits chemical-induced lung carcinogenesis and progression through GNB1 mediated Hippo pathway - Hong-qiang Chen; Na Wang; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Ya-wen Li; Shuang-wu Deng; Zi-yuan Zhou; Wen-bin Liu (Toxicology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Allanite U-Th-Pb geochronology by laser ablation inductively coupled plasma mass spectrometry: Evaluation and development of reference materials with low common Pb - Tao Luo; Mufei Li; Xiaodong Deng; Jiarun Tu; Hongtao Shen; Tom Kapitany; Beining Hu; Wen Zhang; Zhaochu Hu (Chemical Geology, 2025)

Hydrochemistry Predominantly Shapes the Unique Nitrogen-Fixing Bacterial Communities in Tibetan Hot Springs - Zhao-Qi Song; Li Wang; Yaru Ma; Dandan Deng; Yang Song; Feng Liang; Xiangyu Guan; Wen-Jun Li; Hongchen Jiang (Journal of Earth Science, 2025)

Foxa1 disruption enhances human cell integration in human-mouse interspecies chimeras - Li-na Wang; Jun-shuang Jia; Xing-long Yang; Yue-ting Wen; Jing-xian Liu; Deng-ke Li; Xing-rui Chen; Jia-hong Wang; Ji-ke Li; Zhong-xi Huang; Kai-tai Yao (Cell and Tissue Research, 2025)

Quaternized and boronic acid dual-functional CoAg nanozymes for label-free, stable, sensitive, and rapid quantitation detection of the bacterial total concentration - Bin Deng; Shao-Bo Li; Jing-Wen Chen; Fang Liu; Jing Liu; Ji Zhou; Zhong-Kai Zhou; Zai-Tian Wang; Li Li; Zong-Chun Bai; Meng-Xiang Su (Analytica Chimica Acta, 2025)

miR-451a and miR-486-5p: biomarkers for benzene-induced hematotoxicity - Yanrong Lv; Zongxin Li; Yuncong Chen; Fei Qin; Qilong Liao; Zhaorui Zhang; Qifei Deng; Qing Liu; Zihao Long; Qing Wang; Wen Chen; Yongmei Xiao; et al. (Archives of Toxicology, 2025)

Metabolomics Revealed Cadmium Exposure Associated with Alterations in Serum Metabolism in Children - Miaoqian Li; Ping Wan; Lichun Qiao; Xinyue Wen; Huan Deng; Xue Lin; Jingke Lei; Jing Han (Biological Trace Element Research, 2025)

Dual regulation of As release and soil environment by Fe(Ⅱ) assisted steel slag and coal fly ash: Effects and potential mechanisms - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Shan Li; Wen Ni; Siqi Zhang (Journal of Hazardous Materials, 2025)

Enhancing sensitivity and stability of natural pigments in pH-responsive freshness indicators: A review - Rihua Huang; Suxuan Xia; Shuaikun Gong; Jingjing Wang; Wei Zhang; Feifei Zhong; Qinlu Lin; Jing Deng; Wen Li (Food Chemistry, 2025)

Developed metabolomics approach reveals the non-volatile color-contributing metabolites during Keemun congou black tea processing - Mingchun Wen; Wei Hu; Lu Li; Piaopiao Long; Zisheng Han; Jia-Ping Ke; Zhiyang Deng; Mengting Zhu; Liang Zhang (Food Chemistry, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Phthalate exposures, blood coagulation function, and assisted reproductive technology outcomes: Results from the TREE cohort study - Chong Liu; Chang-Jiang Liu; Wen-Qu Tian; Wen Yao; Yu Miao; Min Zhang; Xiao-Qiong Yuan; Yan-Ling Deng; Wen-Qing Lu; Yu-Feng Li; Qiang Zeng (Environmental Research, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

Fore-arc metasomatism by hybrid slab fluids during subduction initiation: Sr–Mg–Ca isotopes of rodingite, western Yarlung Zangbo suture zone - Gui-Fang Ou; Song-Jie Wang; Hao Deng; Wen-Yong Duan; Xu-Ping Li; Hans-Peter Schertl (Chemical Geology, 2025)

Mercury accumulation and transformation in the surface sediments of urban waterscapes in the megacity of Shanghai, China - Hong Deng; Xin Li; Yongjie Wang; Qian Wen; Ming Hung Wong (Journal of Soils and Sediments, 2025)

Genetic relationship analysis and fingerprint construction of some species in the genus Vanda (Orchidaceae) by interprimer binding site (iPBS) markers - Wen-Yi Yin; Xue-Qiang Cui; Qiu-Ju Zhao; Jie-Ling Deng; Chang-Yan Huang; Zi-Bin Zhang; Jia-Wei Li (Genetic Resources and Crop Evolution, 2025)

Assessing traffic emissions during the summer world university games 2023: Insights for multisectoral synergetic decontamination - Hongyi Li; Yifan Wen; Ruoxi Wu; Youchao Wang; Zihang Zhou; Ye Deng; Qinwen Tan; Lei Xiao; Xiaomeng Wu; Shaojun Zhang; Ye Wu (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Identification and characterization of ATP-binding cassette transporters involved in chlorantraniliprole tolerance of model insect Drosophila melanogaster and agricultural pest Spodoptera frugiperda - Lixiang Wang; Bin Wen; Shaoyi Guo; Yujie Han; Zhongyuan Deng; Qian Ding; Xianchun Li (Pesticide Biochemistry and Physiology, 2024)

Role and mechanism of the outer membrane porin LamB in T-2 mycotoxin-mediated extensive drug resistance in Escherichia coli - Fengru Deng; Li Zhao; Ping Wei; Enhua Mai; Meichan Chen; Huixin Yang; Peiqiang Mu; Jun Wu; Jikai Wen; Yiqun Deng (Journal of Hazardous Materials, 2024)

Mode of action underlying toxicity of Camptothecin to Spodoptera frugiperda (Lepidoptera) larvae - Jun-li Lv; Wen-qing Lai; Lei Pang; Xiao-ying Zhang; Kai-yi Zheng; Qiang Zhang; Zhan-peng Lu; Zhi-sheng Wang; Fasihul Lisan; Xue-yang Wang; Lu-feng Hu; Ming-jie Deng (Journal of Asia-Pacific Entomology, 2024)

Combined effects of benzene, toluene, xylene, ethylbenzene, and styrene exposure on hearing loss mediated by oxidative stress at realistic low levels - Yan Liu; Zihao Long; Jingjing Qiu; Qingfei Chen; Aichu Yang; Minghui Xiao; Shanfeng Dang; Yanqun Zhu; Qing Liu; Yanrong Lv; Shuangqi Li; Jingyao Qin; et al. (Environmental Pollution, 2024)

Formation of interior hollow nanocubes derived from cobalt-based metal-organic frameworks via one-step etching for efficient battery desalination - Chengbo Kou; Sareh Vafakhah; Tianchen Li; Guorui Deng; Lei Zhu; Wen Ji; Liping Yang; Chengding Gu; Meng Ding; Lu Guo; Hui Ying Yang (Desalination, 2024)

Metformin Protects Against Acute Kidney Injury Induced by Lipopolysaccharide via Up-Regulating the MCPIP1/SIRT1 Pathway - Wen-long Zhang; Long-jun Zhang; Piao Liang; Hui-long Fang; Xiao-li Wang; Yan-juan Liu; Hua-fei Deng (Biochemical Genetics, 2024)

Vocs pollution and respiratory exposure in commercial and residential underground parking garages - Liyuan Zhang; Weipeng Wu; Jianyue Wang; Yuqi Wang; Yue Zhang; Ning Wang; Shunan Yuan; Jiajun Li; Wenzhuo Xian; Longsheng Deng; Wen Fan (Transportation Research Part D: Transport and Environment, 2024)

Triple-crosslinked double-network alginate/dextran/dendrimer hydrogel with tunable mechanical and adhesive properties: A potential candidate for sutureless keratoplasty - Wen Zhang; Shujing Liu; Lixiang Wang; Boxuan Li; Mengzhen Xie; Yingping Deng; Jialuo Zhang; Huazhang Zeng; Li Qiu; Lisha Huang; Tao Gou; Xiaobo Cen; et al. (Carbohydrate Polymers, 2024)

Silver nanoparticles exhibit ecotoxicological effects via oxidative stress, inflammation, and reproductive toxicity in Asian clam (Corbicula fluminea) - Chun Li; Zhiming Liu; Yang Xu; Jie Pi; Qiushi Zhang; Xiaoying Chen; Chengfeng Zhan; Liang Hu; Jibang Xie; Ziyu Xie; Xinlan Deng; Lixin Wen; et al. (Chemosphere, 2024)

Effect of Humanin and MOTS-c on ameliorating reproductive damage induced by prepubertal cyclophosphamide chemotherapy in male mice - Jinyuan Wang; Wen Wen; Liu Liu; Junhui He; Renhe Deng; Mingxuan Su; Shuhua Zhao; Huawei Wang; Meng Rao; Li Tang (Reproductive Toxicology, 2024)

Multigenerational effects of disperse blue 79 at environmentally relevant concentrations on zebrafish (Danio rerio) fecundity: An integrated approach - Chao Wang; Wen Gu; Shaoping Zhang; Li Li; Jian Kong; Hong Zhi; Juan Liu; Mengmeng Wang; Ke Miao; Qi Li; Jie Yu; Runming Wang; et al. (Journal of Hazardous Materials, 2024)

New insight into the contribution of Ca, Mn, and Mg component to vanadium extraction from vanadium slag - Tangxia Yu; Tao Jiang; Jing Wen; Dongsheng Deng; Lin Zhang; Yuepeng Li; Xiong Yang (Journal of Environmental Chemical Engineering, 2024)

Remediation of As, Sb, and Pb co-contaminated mining soils by using Fe/C based solid wastes: Synergistic effects and field applications - Yuliang Zhang; Pingfeng Fu; Sheng Li; Wei Deng; Wen Ni; Siqi Zhang; Longyan Guo; Shan Li; Xiaofei Wang (Chemical Engineering Journal, 2024)

The Effects of Edge Dislocations on The Corrosion Behavior of Pure Iron in Liquid Lead-Bismuth Eutectic: A Molecular Dynamics Study - Liming Chen; Sijie Liu; Li Wang; Shuyun Gan; Chunmei Wen; Jiaqi Li; Zhongzheng Wu; Xiaoxun He; Shuai Xu; Zhiyong Deng; Vladimir Krsjak; Nabil Daghbouj; et al. (Annals of Nuclear Energy, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Preparation of biomass artificial humic acid/hydrothermal carbon composite and its high-efficiency adsorption of norfloxacin - Wen Chen; Xin Li; Ping Zhao; Xiaping Zhu; Xiang Deng (Journal of Water Process Engineering, 2024)

Emission characteristics of lead and particulate matter from lead and zinc smelters in China - Jiawei Zhang; Xiaohui Sun; Qingru Wu; Jianguo Deng; Zhijian Li; Minneng Wen; Liwen Xu; Yongzheng Gu; Tao Han; Lei Feng; Lei Duan (Journal of Hazardous Materials, 2024)

Targeting m6A mRNA demethylase FTO alleviates manganese-induced cognitive memory deficits in mice - Yi Wen; Zhushan Fu; Jiashuo Li; Mingyue Liu; Xinmiao Wang; Jingqi Chen; Yue Chen; Haocheng Wang; Sihang Wen; Ke Zhang; Yu Deng (Journal of Hazardous Materials, 2024)

In situ U–Pb dating of garnet, vesuvianite, and scheelite from the Nanyangtian tungsten deposit reveals an Early Cretaceous W mineralization event in Southeast Yunnan, China - Xiao-Yu Zhao; Ming-Guo Deng; Wen-Chang Li; Yan-Wen Tang; Ding-Cai Zhang; Sheng-Kang Han; Wen-Bo Song; Qing-Ge Zhang; Jing-Wei Xu (Gondwana Research, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

Triggering Receptor Expressed on Myeloid Cells 2 Alleviated Sevoflurane-Induced Developmental Neurotoxicity via Microglial Pruning of Dendritic Spines in the CA1 Region of the Hippocampus - Li Deng; Shao-Yong Song; Wei-Ming Zhao; Xiao-Wen Meng; Hong Liu; Qing Zheng; Ke Peng; Fu-Hai Ji (Neuroscience Bulletin, 2024)

Spatiotemporal Variability and Environmental Controls of Temperature Sensitivity of Ecosystem Respiration across the Tibetan Plateau - Danrui Sheng; Xianhong Meng; Shaoying Wang; Zhaoguo Li; Lunyu Shang; Hao Chen; Lin Zhao; Mingshan Deng; Hanlin Niu; Pengfei Xu; Xiaohu Wen (Advances in Atmospheric Sciences, 2024)

Investigation of Toxoplasma gondii Infection in Yunnan Semi-fine Wool Sheep (Ovis aries) and wild Rodents in Yunnan, China - Zhao Li; Wen-Jie Cheng; Cai-Qin Deng; Meng-Ling Deng; Hai-Bo Peng; Xing-Quan Zhu; Feng-Cai Zou (Acta Parasitologica, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Deciphering the pathogenic risks of microplastics as emerging particulate organic matter in aquatic ecosystem - Ling-Zi Yin; Xiao-Qing Luo; Jia-Ling Li; Zetao Liu; Li Duan; Qi-Qi Deng; Chen Chen; Shaojun Tang; Wen-Jun Li; Pandeng Wang (Journal of Hazardous Materials, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Electrocatalytic nitrogen reduction to ammonia at low overpotentials based on tungsten carbide doped by non-precious metal single cobalt atoms - Ya Gao; Meng-Jiao Zhu; Xian-He Liu; Guo-Liang Dai; Yi-Wen Zhou; Ze-Da Meng; Li Luo; Tian Gan; Feng Chen; Yu-Yang Zhou; Wen-Wen Deng; Shou-Qing Liu (Chemical Engineering Journal, 2024)

A novel AP2/ERF transcription factor, NtERF10, positively regulates plant height in tobacco - Li Xu; Yong Xu; Jia-rui Jiang; Chang-xin Cheng; Wen-wu Yang; Le-le Deng; Qi-li Mi; Wan-li Zeng; Jing Li; Qian Gao; Hai-ying Xiang; Xue-mei Li (Transgenic Research, 2024)
Ethylene response factors have been shown to be involved in the effects of plant developmental processes and to regulate stress tolerance. The aim of this study was to recognize the regulatory mechanisms of ethylene response factors on tobacco plant height. In this study, a gene-edited mutant (ERF10-KO) and wild type (WT) were utilized as experimental materials. Transcriptome and metabolome analyses were used to investigate the regulatory mechanism of NtERF10 gene editing on plant height in tobacco. Here, through the analysis of differentially expressed genes (DEGs), 2051 genes were upregulated and 1965 genes were downregulated. We characterized the different ERF10-KO and WT plant heights and identified key genes for photosynthesis, the plant hormone signal transduction pathway and the terpene biosynthesis pathway. NtERF10 was found to affect the growth and development of tobacco by regulating the expression levels of the PSAA , PSBA , GLY17 and GGP3 genes. Amino acid metabolism was analyzed by combining analyses of differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs). In addition, we found that members of the bHLH, NAC, MYB, and WRKY transcription factor families have vital roles in regulating plant height. This study not only provides important insights into the positive regulation of the ethylene response factor NtERF10 on plant height during plant growth and development but also provides new research ideas for tobacco molecular breeding.

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Identifying the Interaction Between Tuberculosis and SARS-CoV-2 Infections via Bioinformatics Analysis and Machine Learning - Ze-Min Huang; Jia-Qi Kang; Pei-Zhen Chen; Lin-Fen Deng; Jia-Xin Li; Ying-Xin He; Jie Liang; Nan Huang; Tian-Ye Luo; Qi-Wen Lan; Hao-Kai Chen; Xu-Guang Guo (Biochemical Genetics, 2024)

The complete degradation of 1,2-dichloroethane in Escherichia coli by metabolic engineering - Yong-Dong Deng; Wen-Hui Zhang; Zhi-Hao Zuo; Hao Zhang; Jing Xu; Jian-Jie Gao; Bo Wang; Zhen-Jun Li; Xiao-Yan Fu; Li-Juan Wang; Yu Wang; Yong-Sheng Tian; et al. (Journal of Hazardous Materials, 2024)

Label analysis and molecular identification of Japanese Seafood Products purchased on Chinese e-commerce - Xia Zhang; Chiara Malloggi; Alice Giusti; Weide Deng; Zhenzhu Sun; Yuan Li; Jing Guo; Hongyuan Peng; Lara Tinacci; Lin Gao; Andrea Armani; Jing Wen (Food Control, 2024)

The selection of animal models influences the assessment of anti-tumor efficacy: promising sialic acid-conjugate modified liposomes demonstrate remarkable therapeutic effects in diverse mouse strains - Lu Wei; Lin Lin; Jia Wang; Xinying Guan; Wen Li; Yangxu Gui; Shupei Liao; Mingyang Wang; Jiaqi Li; Yihui Deng; Yanzhi Song (Drug Delivery and Translational Research, 2024)

Plastome structure, phylogeny and evolution of plastid genes in Reevesia (Helicteroideae, Malvaceae) - Li-Yang Geng; Tian-Yi Jiang; Xin Chen; Qiang Li; Jian-Hui Ma; Wen-Xiang Hou; Chen-Qian Tang; Qin Wang; Yun-Fei Deng (Journal of Plant Research, 2024)

Polymethoxyflavones from citrus peel: advances in extraction methods, biological properties, and potential applications - Qiong Peng; Yao Zhang; Mingxuan Zhu; Feng Bao; Jing Deng; Wen Li (Critical Reviews in Food Science and Nutrition, 2024)

Carbon nanotube incorporated quaternized lignin-based loose nanofiltration membrane toward dye/salt separation - Zhenyu He; Na Zhang; Li Zhao; Zhenghua Li; Wanling Cui; Yuangang Zhu; Yi Wang; Huining Deng; Chengrun Si; Wen Bo; Jie Zhou; Shicai Xu; et al. (Journal of Environmental Chemical Engineering, 2024)

Endocrine disrupting chemicals in children's and their parents' urine: Is the exposure related to the Chinese and Western lifestyle? - Na Li; Jing Liu; Guangguo Ying; John Chi-Kin Lee; Ting Fan Leung; Adrian Covaci; Wen-Jing Deng (International Journal of Hygiene and Environmental Health, 2024)

Corrigendum to “Molecular authentication of surimi-based products (fish cakes, 鱼糕) sold on the Chinese e-commerce: Traditional (DNA barcoding) and innovative techniques (metabarcoding) to tackle seafood fraud” [Food Control 155 (2024) 110110] - Xia Zhang; Alice Giusti; Zhenzhu Sun; Yuan Li; Jing Guo; Weide Deng; Yanfei Chen; Ailan He; Hongyuan Peng; Lara Tinacci; Andrea Armani; Jing Wen (Food Control, 2024)

Advances in dual-functional packaging: Visual monitoring of food freshness using plant essential oils and pH-sensitive natural pigments - Qiong Peng; Feng Bao; Min Tang; Feifei Zhong; Wen Li; Jing Deng; Qinlu Lin; Mingli Yan; Zavuga Zuberi (Food Control, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Behavioral responses of Nesidiocoris tenuis (Reuter) to different monochromatic lights and light intensities - Zhen Chen; Wen Fu; Chun-Fu Zhang; Hong-Mei Li; Jun-Jun Zhang; Deng-Ji Lou; Kai-Fei Guo (Journal of Plant Diseases and Protection, 2024)

Subregions of the fusiform gyrus are differentially involved in the attentional mechanism supporting visual mental imagery in depression - Jun-He Zhou; Bin-Kun Huang; Di Wang; Bai-Le Ning; Xue-Song Liang; Chang-Hong Li; Zeng-Jian Wang; Ying Deng; Xi-Chang Huang; De-Long Zhang; Wen-Bin Fu (Brain Imaging and Behavior, 2024)

Toward intelligent food packaging of biosensor and film substrate for monitoring foodborne microorganisms: A review of recent advancements - Feng Bao; Zhao Liang; Jing Deng; Qinlu Lin; Wen Li; Qiong Peng; Yong Fang (Critical Reviews in Food Science and Nutrition, 2024)

Stomatohabitans albus gen. nov., sp. nov., an oral living facultative anaerobic actinobacteria isolated form Steller sea lion, and proposal of Stomatohabitantaceae fam. nov. and Stomatohabitantales ord. nov - Zi-Wen Yang; Wen-Li Liu; Peng Zhang; Dan-Yuan Guo; Hong-Chuan Wang; Jia-Ling Li; Pan-Deng Wang; Gui-Xin Dong; Guo-Xing Nie; Wen-Jun Li (Systematic and Applied Microbiology, 2024)

Transoceanic ships as a source of alien dinoflagellate invasions of inland freshwater ecosystems - Lixia Shang; Zhangxi Hu; Yunyan Deng; Jing Li; Yuyang Liu; Xiaoying Song; Xinyu Zhai; Zifeng Zhan; Wen Tian; Jinxiang Xu; Yangchun Han; Hao Shen; et al. (Harmful Algae, 2024)

Simultaneous removal of As(V) and sulfamethazine from water in FeS2-H2O2 system - Wen Li; Shanshan Yang; Shuiyu Sun; Tianming Wang; Qi Yao; Jingyi Zhan; Shanwen Ye; Yating Liang; Yunzhuo Deng; Wenxiang Wang; Hongsheng Fang; Yunmei Cai (Chemical Engineering Journal, 2024)

A review of solid wastes-based stabilizers for remediating heavy metals co-contaminated soil: Applications and challenges - Yuliang Zhang; Pingfeng Fu; Wen Ni; Siqi Zhang; Sheng Li; Wei Deng; Wentao Hu; Jia Li; Fuyun Pei; Linfeng Du; Yueling Wang (Science of The Total Environment, 2024)

Atmospheric VOCs in an industrial coking facility and the surrounding area: Characteristics, spatial distribution and source apportionment - Meicheng Wen; Weiqiang Deng; Jin Huang; Shu Zhang; Qinhao Lin; Chao Wang; Shengtao Ma; Wanjun Wang; Xin Zhang; Guiying Li; Taicheng An (Journal of Environmental Sciences, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Numerical simulation analysis of debris filtration in the bottom nozzle - Shuang Deng; Quan-yao Ren; Jing Zhang; Xin Duan; Fa-wen Zhu; Yong Xin; Xin-Yu Yang; Quan Li; Ying-wei Wu (Annals of Nuclear Energy, 2024)

Occurrence of BTX and PAHs in underground drinking water of coking contaminated sites: Linkage with altitude and health risk assessment by boiling-modified models - Chao Wang; Wanjun Wang; Shaobin Shao; Weiqiang Deng; Congqing Wang; Xinyuan Liu; Hailing Li; Meicheng Wen; Xin Zhang; Guiying Li; Taicheng An (Science of The Total Environment, 2024)

Nano polystyrene microplastics could accumulate in Nile tilapia (Oreochromis niloticus): Negatively impacts on the intestinal and liver health through water exposure - Di Wu; Xing Lu; Li-Xue Dong; Juan Tian; Jin Deng; Lei Wei; Hua Wen; Shan Zhong; Ming Jiang (Journal of Environmental Sciences, 2024)

Virgin coconut oil: A comprehensive review of antioxidant activity and mechanisms contributed by phenolic compounds - Yu-Qing Zeng; Jin-Tao He; Bo-Yong Hu; Wen Li; Jing Deng; Qin-Lu Lin; Yong Fang (Critical Reviews in Food Science and Nutrition, 2024)

Crop plant automatic detecting based on in-field images by lightweight DFU-Net model - Hui Shi; Dongyuan Shi; Shengjie Wang; Wei Li; Haojun Wen; Hongtao Deng (Computers and Electronics in Agriculture, 2024)

Sustainable valorizing high-protein feather waste utilization through solid-state fermentation by keratinase-enhanced Streptomyces sp. SCUT-3 using a novel promoter - Wen-Jun Lu; Ming-Shu Zhang; De-Lin Lu; Zhi-Wei Li; Zhen-Dong Yang; Lei Wu; Jing-Tao Ni; Wei-Dong Chen; Jun-Jin Deng; Xiao-Chun Luo (Waste Management, 2024)

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Multi-isotopic composition (Li and B isotopes) and hydrochemistry characterization of the Lakko Co Li-rich salt lake in Tibet, China: Origin and hydrological processes - Zhengyan Li; Mao-Yong He; Binkai Li; Xueqin Wen; Jiangdi Zhou; Yuanyuan Cheng; Ning Zhang; Li Deng (Journal of Hydrology, 2024)

Novel modified semi-carbonized fiber prepared using discarded clothes for derisking Cu(II) and Pb(II) contaminated water - Hong-yan Deng; Yin-fei Wang; Meng-ting Guo; Wen-bin Li; Min Li; Chu-tong Yu (Journal of Environmental Management, 2024)

A colorimetric and phosphorescent dual-mode nanosensing platform for the sensitive detection of tobramycin in dairy products - Songlin Liu; Mina Wang; Hui Deng; Xin Deng; Ying Xiong; Qian Wen; Wang Li; Jiali Ren; Xiangjin Fu; Yanni Chen (Food Bioscience, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Application of solid electrolytes in electrochemical reduction of CO2 or O2 - Jiayue Li; Zhuowen Wang; Sibei Liu; Zhonglin Chen; Jixian Yang; Zhiqiang Chen; Ang Li; Qinxue Wen; Li Wang; Shan Qiu; Chongwei Cui; Huiyuan Deng; et al. (Chemical Engineering Journal, 2024)

Exploring intrinsic distribution of phytoplankton relative abundance and biomass in combination with continental-scale field investigation and microcosm experiment - Sisi Ye; Ling Wen; Li Gao; Junyi Zhang; Haihan Zhang; Songqi Yang; En Hu; Jianming Deng; Man Xiao; Arash Zamyadi; Baozhu Pan; Ming Li (Water Research, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Pressure–temperature–time path of ultrahigh-pressure metamorphic terranes constrained by zircon petrochronology: A case study of orthogneisses from the northern Sulu belt, China - Peng Feng; Hao Deng; Yang Zhang; Qing-Lin Sui; Hai-Yang He; Yan-Shi Xie; Liang Chen; Xian-Zhe Duan; Wen-Zhou Xiao; Xia-Wen Li; Nan Li (Journal of Asian Earth Sciences, 2024)

Molecular authentication of surimi-based products (fish cakes, 鱼糕) sold on the Chinese e-commerce: Traditional (DNA barcoding) and innovative techniques (metabarcoding) to tackle seafood fraud - Xia Zhang; Alice Giusti; Zhenzhu Sun; Yuan Li; Jing Guo; Weide Deng; Yanfei Chen; Ailan He; Hongyuan Peng; Lara Tinacci; Andrea Armani; Jing Wen (Food Control, 2024)

Labelling compliance assessment and molecular authentication of Grilled Fish Products Sold on Chinese e-commerce: Traceability issues related to the use of umbrella trade names - Xia Zhang; Tinacci Lara; Zhenzhu Sun; Yuan Li; Jing Guo; Weide Deng; Yanfei Chen; Ailan He; Hongyuan Peng; Andrea Armani; Wen Jing (Food Control, 2024)

Transcriptome analysis revealed the function of five tandemly duplicated nAChRs in the transplantation immunity in pearl oyster Pinctada fucata martensii - Min Yang; Ming Zhang; Xin lei Li; Yue wen Deng; Yu Jiao (Fish & Shellfish Immunology, 2024)

An insight into the health beneficial of probiotics dairy products: a critical review - JinTao He; Wen Li; Jing Deng; QinLu Lin; Jie Bai; Lin Zhang; Yong Fang (Critical Reviews in Food Science and Nutrition, 2023)

Comparative miRNA-seq analysis revealed molecular mechanisms of red color formation in the early developmental stages of Plectropomus leopardus - Xi Liu; Mouyan Jiang; Simin Wen; Kaixiang Zhang; Yucong Hong; Kaihui Sun; Xianwu Deng; Yang Huang; Gang Shi; Changxu Tian; Huapu Chen; Guangli Li; et al. (Frontiers in Marine Science, 2023)
MicroRNAs (miRNAs) are endogenous small non-coding RNAs that play important roles in several biological processes, including the regulation of body color. Leopard coral grouper ( Plectropomus leopardus ) is a valuable marine aquaculture fish; however, at present, there are no published reports on its early body color development. The skin color of P. leopardus undergoes a transition from transparent to red from 26 days post-hatching (dph) to 30 dph. In this study, we performed miRNA sequencing on 26 dph (Transparent, PT) and 30 dph (Red, PR) skin samples of P. leopardus to explore the molecular mechanism underlying red color formation. A total of 44.31 M and 37.55 M clean tags were obtained from PT and PR group, respectively. Among these tags, 981 miRNAs were identified, including 493 known and 488 novel miRNAs. A total of 106 differentially expressed miRNAs (DEMs) were identified in PT vs. PR, with 43 up-regulated and 63 down-regulated miRNAs in the PR group, compared to the PT group (|fold change| > 2 and p-value < 0.05). A miRNA-mRNA network based on 18 candidate miRNAs and 53 target genes related to pigmentation, and KEGG enrichment analysis of the target genes of all DEMs, revealed that miRNAs involved in the formation of red skin color were mainly related to: 1) the inhibition of melanin synthesis (miR-141-z, miR-206-z, miR-206-y, miR-27-z, miR-137-y, miR-204-x, miR-204-y, miR-211-x, miR-211-z); 2) chromatophore development (miR-206-z, miR-206-y, miR-499-y, miR-1-z, miR-2188-x, miR-423-x); and 3) carotenoid metabolism (miR-204-x, miR-204-y, miR-499-y). This study demonstrates the potential role of miRNAs in red color formation and lays the foundation for the molecular mechanism of body color polymorphism in P. leopardus .

Resource recovery and valorization of food wastewater for sustainable development: An overview of current approaches - JinTao He; SuXuan Xia; Wen Li; Jing Deng; QinLu Lin; Lin Zhang (Journal of Environmental Management, 2023)

Purification and characterization of the low molecular weight xylanase from Bacillus cereus L-1 - Ge Zhang; Zhihao Li; Guoqiang Chen; Liang Zhang; Wen Cai; Shuaijun Deng; Haibo Zhang; Lijun Wu; Hongtao Li; Haobao Liu (Brazilian Journal of Microbiology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

The influence of anthropogenic climate change on meteorological drought in the Lancang-Mekong River basin - Xingye Han; Qiongfang Li; Xiaoqiang Yang; Shuhong Xu; Zhenhua Zou; Mingjiang Deng; Wen Wang (Journal of Hydrology, 2023)

Determination of the effects of pre-harvest bagging treatment on kiwifruit appearance and quality via transcriptome and metabolome analyses - Deng-wei Jue; Xue-lian Sang; Zhe-xin Li; Wen-lin Zhang; Qin-hong Liao; Jianmin Tang (Food Research International, 2023)

A review on takeaway packaging waste: Types, ecological impact, and disposal route - Yu Zhuo; JinTao He; Wen Li; Jing Deng; QinLu Lin (Environmental Pollution, 2023)

Potential role of mesenchymal stem cells in T cell aging - Xianmei Zhong; Jie Chen; Bo Wen; Xu Wu; Mingxing Li; Fukuan Du; Yu Chen; Shuai Deng; Yueshui Zhao; Jing Shen; Zhangang Xiao (Journal of Molecular Medicine, 2023)

Fragmentation process of soil aggregates under concentrated water flow in red soil hilly region with different land use patterns - Li-li Wen; Jin-yue Wang; Yu-song Deng; Xiao-qian Duan (Journal of Mountain Science, 2023)

Effect of low-temperature stress on transcriptome and Na+/K+-ATPase changes in Oreochromis niloticus gill tissues - Zhe Li; Luting Wen; Junqi Qin; Zhong Chen; Xianhui Pan; Kangqi Zhou; Yin Huang; Qian Deng; Yong Lin; Xuesong Du (Ichthyological Research, 2023)

Effect of short-term ambient air pollution exposure on early miscarriage and pregnancy hormones with critical window identification - Qing Xu; Quanquan Guan; Yingying Lu; Jie Xu; Siting Deng; Chao Dong; Xiaochen Zhang; Wen Li; Yankai Xia (Journal of Hazardous Materials, 2023)

Improvement of catalytic activity of sorbose dehydrogenase for deoxynivalenol degradation by rational design - Danyang Li; Guoqiang Liang; Peiqiang Mu; Jinquan Lin; Jiarun Huang; Chongwen Guo; Yang Li; Ruqin Lin; Jun Jiang; Jun Wu; Yiqun Deng; Jikai Wen (Food Chemistry, 2023)

Alsobacter ponti sp. nov., a novel denitrification and sulfate reduction bacterium isolated from Pearl River sediment - Qi-Qi Deng; Xiao-Qing Luo; Shan-Hui Li; Jia-Ling Li; Pan-Deng Wang; Yang Yuan; Zi-Wen Yang; Wen-Jun Li (Antonie van Leeuwenhoek, 2023)

Heavy metals distribution characteristics, source analysis, and risk evaluation of soils around mines, quarries, and other special areas in a region of northwestern Yunnan, China - Xin Liu; Huajian Chi; Zhiqiang Tan; Xiaofang Yang; Yiping Sun; Zongtao Li; Kan Hu; Fangfang Hao; Yong Liu; Shengchun Yang; Qingwen Deng; Xiaodong Wen (Journal of Hazardous Materials, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Effect and Mechanism of Sodium Butyrate on Neuronal Recovery and Prognosis in Diabetic Stroke - Ting-ting Li; Deng-ming Zhao; Yu-ting Wei; Jing-bo Li; Xue-fei Li; Qiang Wan; Xin Zhang; Xiang-nan Liu; Wan-chao Yang; Wen-zhi Li (Journal of Neuroimmune Pharmacology, 2023)

Bibliometric analysis of climate change and water quality - Jin Gao; Shiying Zhu; Dehao Li; Haibo Jiang; Guangyi Deng; Yang Wen; Chunguang He; Yingyue Cao (Hydrobiologia, 2023)

Non-monotonic Association Between Chlorinated Polyfluorinated Ether Sulfonic Acids Exposure and the Risk of Overweight/Obesity Status in Adults - Chu Chu; Qiu-Ling Fang; Xin-Xin Cui; Peng-Xin Dong; Zhengmin Qian; Stephen Edward McMillin; Steven W. Howard; Yan-Qiu Ou; Qing-Qing Li; Lu-Yin Wu; Li-Xia Liang; Shuang-Jian Qin; et al. (Exposure and Health, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Adaptive mechanisms of Bacillus to near space extreme environments - Aihua Deng; Tiantian Wang; Junyue Wang; Lai Li; Xueliang Wang; Li Liu; Tingyi Wen (Science of The Total Environment, 2023)

Synergism of NiFe layered double hydroxides/phosphides and Co-NC nanorods array for efficient electrocatalytic water splitting - Tao You; Kuan Deng; Peng Liu; Xingbin Lv; Wen Tian; Hongjiao Li; Junyi Ji (Chemical Engineering Journal, 2023)

Star-like, dopant-free, corannulene-cored hole transporting materials for efficient inverted perovskite solar cells - Ming-Wei An; Bolin Li; Bin-Wen Chen; Zuo-Chang Chen; Han-Rui Tian; Lin-Long Deng; Xugang Guo; Zhou Xing (Chemical Engineering Journal, 2023)

Wnt/β-Catenin Promotes the Osteoblastic Potential of BMP9 Through Down-Regulating Cyp26b1 in Mesenchymal Stem Cells - Xin-Tong Yao; Pei-pei Li; Jiang Liu; Yuan-Yuan Yang; Zhen-Ling Luo; Hai-Tao Jiang; Wen-Ge He; Hong-Hong Luo; Yi-Xuan Deng; Bai-Cheng He (Tissue Engineering and Regenerative Medicine, 2023)

Alkalihalobacillus deserti sp. nov., Isolated from the Saline–Alkaline Soil - Zulihumaer Rouzi; Yu-Qian Li; Muyesaier Aosiman; Dilireba Abudourousuli; Lan Liu; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Deng-Di An; Wen-Jun Li (Current Microbiology, 2023)

Selective CDK9 knockdown sensitizes TRAIL response by suppression of antiapoptotic factors and NF-kappaB pathway - Qian Yuan; Kui Su; Shuyi Li; Xinyi Long; Lang Liu; Jianwu Sun; Xin Yuan; Minghui Yang; Rui Tian; Wanting Zhang; Zhujie Deng; Quanjiang Li; et al. (Apoptosis, 2023)

Distribution of hydrogen isotope in the soil around the Qinshan Nuclear Power Plant - Jie Liang; Wen-yu Cheng; Jing-lin Li; Xiao-chong Xue; Ke Deng; Chao-fei Liang; Lin Du; Qin Zhang; Wei Liu (Journal of Environmental Radioactivity, 2023)

Surface-bulk-passivated perovskite films via 2-thiophenemethylammonium bromide and PbBr2 for air-processed perovskite solar cells with high-stability - Lingling Wen; Yaxin Deng; Gangyi Zeng; Guangyao Liu; Xin Li (Chemical Engineering Journal, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

N-Fluorobenzenesulfonimide as a multifunctional electrolyte additive for co-stabilizing dual-electrodes of lithium metal batteries with enhanced electrochemical performance - Xianjun Weng; Yanyang Qin; Xinyu Da; Yuanjun Zhao; Xuetian Deng; Bo Wen; Manying Cui; Xiangkai Yin; Yaqiong Su; Jiangxuan Song; Shujiang Ding; Xiaofei Hu; et al. (Chemical Engineering Journal, 2023)

Insights into landslide development and susceptibility in extremely complex alpine geoenvironments along the western Sichuan–Tibet Engineering Corridor, China - Siyuan Zhao; Fuchu Dai; Jianhui Deng; Hong Wen; Hua Li; Fei Chen (CATENA, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Dataset of Comparative Observations for Land Surface Processes over the Semi-Arid Alpine Grassland against Alpine Lakes in the Source Region of the Yellow River - Xianhong Meng; Shihua Lyu; Zhaoguo Li; Yinhuan Ao; Lijuan Wen; Lunyu Shang; Shaoying Wang; Mingshan Deng; Shaobo Zhang; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2023)
Thousands of lakes on the Tibetan Plateau (TP) play a critical role in the regional water cycle, weather, and climate. In recent years, the areas of TP lakes underwent drastic changes and have become a research hotspot. However, the characteristics of the lake-atmosphere interaction over the high-altitude lakes are still unclear, which inhibits model development and the accurate simulation of lake climate effects. The source region of the Yellow River (SRYR) has the largest outflow lake and freshwater lake on the TP and is one of the most densely distributed lakes on the TP. Since 2011, three observation sites have been set up in the Ngoring Lake basin in the SRYR to monitor the lake-atmosphere interaction and the differences among water-heat exchanges over the land and lake surfaces. This study presents an eight-year (2012–19), half-hourly, observation-based dataset related to lake–atmosphere interactions composed of three sites. The three sites represent the lake surface, the lakeside, and the land. The observations contain the basic meteorological elements, surface radiation, eddy covariance system, soil temperature, and moisture (for land). Information related to the sites and instruments, the continuity and completeness of data, and the differences among the observational results at different sites are described in this study. These data have been used in the previous study to reveal a few energy and water exchange characteristics of TP lakes and to validate and improve the lake and land surface model. The dataset is available at National Cryosphere Desert Data Center and Science Data Bank.

miR-10a-3p Participates in Nacre Formation in the Pearl Oyster Pinctada fucata martensii by Targeting NPY - Min Yang; Xin lei Li; Yu ting Zhang; Yue wen Deng; Yu Jiao (Marine Biotechnology, 2023)

Identification and characterization of IgNAR and VNAR repertoire from the ocellate spot skate (Okamejei kenojei) - Jianqing Wen; Jinyu Gong; Pengwei Li; Penghui Deng; Mengsi Sun; Yujie Wu; Chenxi Tian; Hao Wang; Yunchen Bi (Frontiers in Marine Science, 2023)
Elasmobranchs are crucial for comparative studies of evolution, as they belong to the most ancient vertebrate lineages that survived numerous extinction events and persist until today. The immunoglobulin new antigen receptor (IgNAR) found in sharks and heavy-chain-only antibody (HCAb) found in camelidae are products of convergent evolution. Although it was previously believed that IgNAR emerged 220 million years ago, before the divergence of sharks and skates, there is limited evidence to support this. In this study, we provide data supporting the existence of IgNAR in the ocellate spot skate ( Okamejei kenojei ) mononuclear cell transcriptome and peripheral blood serum. Additionally, we characterize the germline gene configuration of the ocellate spot skate IgNAR V domain. The ocellate spot skate IgNAR structure prediction and VNAR crystal structure exhibit high similarity to their shark counterparts. These data strongly suggest that IgNAR in both sharks and skates share a common ancestor. Sequencing of the ocellate spot skate VNAR repertoire provided crucial data for further understanding of the IgNAR generation. Notably, we discovered that approximately 99% of the ocellate spot skate VNARs belonged to type IV. This represents an exceptionally high proportion of type IV within the VNAR repertoire, which has not been documented in previously studied elasmobranchs. This unique characteristic of the ocellate spot skate VNAR adds essential structural diversity to the naïve VNAR library from elasmobranchs and could potentially benefit the development of pharmaceutical drugs.

Preparation, characterization and safety evaluation of Ligusticum chuanxiong essential oils liposomes for treatment of cerebral ischemia-reperfusion injury - Yu Long; Shuang Yu; Dan Li; Ai Shi; Yin Ma; Jie Deng; Xiao-qiu Li; Jing Wen; Yuan-yuan Wu; Yue Hu; Xiao-fang He; Nan Li; et al. (Food and Chemical Toxicology, 2023)

Intercropped soybean boosts nitrogen benefits and amends nitrogen use pattern under plastic film mulching in the semiarid maize field - Wei Zhang; Yong-Xian Wei; Aziz Khan; Jun-Sheng Lu; Jun-Lan Xiong; Shuang-Guo Zhu; Xiang-Wen Fang; Wei Wang; Meng Hao; Ling Zhao; Xiao-Lin Zhang; Jian-Ming Deng; et al. (Field Crops Research, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

Methcathinone Increases Visually-evoked Neuronal Activity and Enhances Sensory Processing Efficiency in Mice - Jun Zhou; Wen Deng; Chen Chen; Junya Kang; Xiaodan Yang; Zhaojuan Dou; Jiancheng Wu; Quancong Li; Man Jiang; Man Liang; Yunyun Han (Neuroscience Bulletin, 2023)

An in-situ strategy to construct uracil-conjugated covalent organic frameworks with tunable fluorescence/recognition characteristics for sensitive and selective Mercury(II) detection - Xi-Rui Deng; A-Wei Hu; Sheng-Qian Hu; Wen-Li Yang; Chen Sun; Sai-Jin Xiao; Gui-Ping Yang; Qiong-Qing Zheng; Ru-Ping Liang; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Exposure to cadmium induced gut antibiotic resistance genes (ARGs) and microbiota alternations of Babylonia areolata - Wang Zhao; Qian Han; Rui Yang; Weigeng Wen; Zhenghua Deng; Huan Li; Zhongming Zheng; Zhenhua Ma; Gang Yu (Science of The Total Environment, 2023)

Distribution characteristics, air-water exchange, ozone formation potential and health risk assessments of VOCs emitted from typical coking wastewater treatment process - Chao Wang; Wanjun Wang; Weiqiang Deng; Shu Zhang; Shaobin Shao; Meicheng Wen; Guiying Li; Taicheng An (Science of The Total Environment, 2023)

The impact of temperature and precipitation on all-infectious-, bacterial-, and viral-diarrheal disease in Taiwan - Gerry Andhikaputra; Amir Sapkota; Yu-Kai Lin; Ta-Chien Chan; Chuansi Gao; Li-Wen Deng; Yu-Chun Wang (Science of The Total Environment, 2023)

Associations between trace level thallium and multiple health effects in rural areas: Chinese Exposure and Response Mapping Program (CERMP) - Yun-Jiang Yu; Zhen-Chi Li; Yang Zhou; Chen-Yin Dong; Hong-Xuan Kuang; Tong Zheng; Ming-Deng Xiang; Xi-Chao Chen; Hong-Yan Li; Xiao-Wen Zeng; Shu-Li Xu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Detrimental effect of dissolved natural organic matter on molybdenite flotation - Jialei Li; Wen Deng; Zhicheng Liu; Bin Pei; Shuai Ning; Zi Cai; Ruizeng Liu (Minerals Engineering, 2023)

Heavy-metal resistant bio-hybrid with biogenic ferrous sulfide nanoparticles: pH-regulated self-assembly and wastewater treatment application - Xian-Zhong Fu; Jie Wu; Jie Li; Jian Ding; Shuo Cui; Xue-Meng Wang; Yun-Jie Wang; Hou-Qi Liu; Xin Deng; Dong-Feng Liu; Wen-Wei Li (Journal of Hazardous Materials, 2023)

Antibiotic removal and microbial response mechanism in constructed wetlands treating aquaculture wastewater containing veterinary drugs - Yang-yang Deng; Meng-yao Zou; Wen Liu; Ying-li Lian; Qin-mei Guo; Xiao-meng Zhang; Dan A (Journal of Cleaner Production, 2023)

Glutathione inhibited starch digestion: Structural and kinetic analysis of substrate and α-amylase - Yi-Fan Tang; Wen-Xi Zhan; Mi-Zhuan Li; Lei Wang; Jie-Ying Wei; Jun-ling Deng; Zhong-Xiu Chen (Food Chemistry, 2023)

Aggregating-agent-assisted surface-enhanced Raman spectroscopy–based detection of acrylamide in fried foods: A case study with potato chips - Zhi-hao Ye; Xiao-tong Chen; Hai-yan Zhu; Xiao-qian Liu; Wen-hui Deng; Wei Song; Da-xiang Li; Ru-yan Hou; Hui-mei Cai; Chuan-yi Peng (Food Chemistry, 2023)

Study on the safety and excellent probiotic properties of fermentation strains isolated from traditional dry-cured duck for starter development - Xiao-min Li; Jie-ying Deng; Wen Nie; Cong Li; Bao-cai Xu (Food Bioscience, 2023)

Probing the stability of perovskite solar cell under working condition through an ultra-thin silver electrode: Beyond the halide ion diffusion and metal diffusion - Hao Li; Zheng Yan; Min Li; Xiaoyan Wen; Shuo Deng; Sisi Liu; Wallace C.H. Choy; Lijie Li; Ming-Yu Li; Haifei Lu (Chemical Engineering Journal, 2023)

Highly efficient shrimp shell recovery by solid-state fermentation with Streptomyces sp. SCUT-3 - De-Lin Lu; Ming-Shu Zhang; Jun-Jin Deng; Wen-Jun Lu; Zhen-Dong Yang; Zhi-Wei Li; Yu-Chen Chen; Xiao-Chun Luo (Chemical Engineering Journal, 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Microplastics removal and characteristics of a typical multi-combination and multi-stage constructed wetlands wastewater treatment plant in Changsha, China - Yuannan Long; Zhenyu Zhou; Xiaofeng Wen; Jianwu Wang; Ruihao Xiao; Wenming Wang; Xiwei Li; Xu Lai; You Zhang; Chaoping Deng; Jinsong Cao; Lingshi Yin (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Urinary phthalate metabolites and the risk of endometrial polyp: A pilot study from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Wen Yao; Qing-Yun Yao; Yong Huang; Ni-Jie Li; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Yu-Feng Li; et al. (Environmental Pollution, 2023)

Supercooled sugar alcohols stabilized by alkali hydroxides for long-term room-temperature phase change solar-thermal energy storage - Xiaoxiang Li; Jingyi Zhang; Yizhe Liu; Yangzhe Xu; Kehang Cui; Zhenpeng Yao; Benwei Fu; Chengyi Song; Wen Shang; Peng Tao; Tao Deng (Chemical Engineering Journal, 2023)

Effect of divalent cations on electrochemiluminescence of metal-organic frameworks in bioassay - Xuyu Feng; Bin Li; Longyi Zhu; Wen Chen; Ying Wu; Yanru Duan; Meiyan Song; Ying Wan; Shengyuan Deng (Analytica Chimica Acta, 2023)

Relation of Carotid Plaque Features Detected with Ultrasonography-Based Radiomics to Clinical Symptoms - Zhe Huang; Xue-Qing Cheng; Hong-Yun Liu; Xiao-Jun Bi; Ya-Ni Liu; Wen-Zhi Lv; Li Xiong; You-Bin Deng (Translational Stroke Research, 2022)

Structural deformation, metallogenic epoch and genetic mechanism of the Woxi Au-Sb-W deposit, Western Hunan Province, South China - Bin Li; Deru Xu; Daoyuan Bai; Guoxiang Chi; Junfeng Dai; Cheng Gao; Teng Deng; Shaohao Zou; Wen Ma; Guojian Wang; Yuexin Ling; Guangqian Zeng; et al. (Science China Earth Sciences, 2022)

Genome-wide analysis of cysteine proteases (CP) in apple (Malus domestica) and functional characterization of MdCP37 in response to drought stress - XingYao Gong; WenPeng Deng; Binbin Wen; Wei Xiao; Ling Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Uncovering expression and functional analysis of newly discovered high-affinity K+ transporter family members from sugarcane - Hai-bin Luo; Cheng-mei Huang; Yuan-wen Wei; Hui-ming Zhu; Hui-qing Cao; Sheng-li Jiang; Zhi-nian Deng; Kai-chao Wu; Lin Xu (Journal of Plant Biochemistry and Biotechnology, 2022)

Fractionation mechanism of iron isotopes in highly fractionated granites from the Xinxian Pluton, Western Dabie Orogen, Central China - Chenglai Deng; Changqing Hu; Qiuyu Wen; Wenbin Yang; Wu Li (Acta Geochimica, 2022)

The inhibition of CFTR in the descended testis of SD rats with unilateral cryptorchidism induced by di-(2-ethylhexyl) phthalate (DEHP) - Xiangliang Tang; Dian Li; Tianxin Zhao; Shibo Zhu; Xiaofeng Gao; Rui Zhou; Fuming Deng; Wen Fu; Wei Jia; Guochang Liu (Environmental Science and Pollution Research, 2022)

Maternal exposure to cooking oil fumes during pregnancy and autistic‐like behaviors in Chinese preschoolers - Jian-Hui Yang; Esben Strodl; Chuan-An Wu; Xiang-Yu Hou; Xiao-Na Yin; Guo-Min Wen; Deng-Li Sun; Dan-Xia Xian; Jing-Yi Chen; Ying-Jie Chen; Jing Chen; Wei-Qing Chen (Environmental Science and Pollution Research, 2022)

Toward improvements for enhancement the productivity and color value of Monascus pigments: a critical review with recent updates - JinTao He; MingXi Jia; Wen Li; Jing Deng; JiaLi Ren; FeiJun Luo; Jie Bai; Jun Liu (Critical Reviews in Food Science and Nutrition, 2022)

Phylogenetic analyses, morphological studies, and muscarine detection reveal two new toxic Pseudosperma (Inocybaceae, Agaricales) species from tropical China - Li-Na Zhao; Wen-Jie Yu; Lun-Sha Deng; Jian-Hua Hu; Yu-Peng Ge; Nian-Kai Zeng; Yu-Guang Fan (Mycological Progress, 2022)

Long-term changes in zooplankton in the Changjiang estuary from the 1960s to 2020 - Ping Du; Wen-Jian Ye; Bang-Ping Deng; Ming Mao; Yuan-Li Zhu; Fang-Ping Cheng; Zhi-Bing Jiang; Lu Shou; Quan-Zhen Chen (Frontiers in Marine Science, 2022)
The Changjiang estuary (CJE) is a large estuary that is affected by multiple anthropogenic stressors and climate change. The long-term trend of zooplankton in the CJE is an important indicator of the ecological response to stressors. We applied the Mann–Kendall trend analysis and Pettitt test to detect the trend and breakpoints of the biomass of the large mesozooplankton (LMZ; 505–20 000 μm) in four seasons, abundance of main LMZ taxa in summer from the 1960s to 2020, and abundance of dominant species in summer from 2000 to 2020 in the CJE. Results showed that LMZ biomass increased significantly during spring and summer, and the breakpoints both occurred in the 1980s. After the breakpoint, the mean biomass increased from 142.88 to 429.42 mg/m 3 in spring and from 296.28 to 723.92 mg/m 3 in summer. After 2000, the abundance of Copepoda in summer increased by more than 10 times compared to the 1960s. Under the conditions of warming and increased dinoflagellate abundance in the CJE, the abundance of the warm-water and omnivorous small calanoid copepod Paracalanus aculeatus increased significantly. Meanwhile, the significant decrease in the abundance of the temperate brackish species Labidocera euchaeta was probably mainly related to warming. The rapid changes in LMZ biomass during the late 1980s and mid-1990s is probably the result of a combination of enhanced bottom–up support, reduced top–down pressure, and promotion of temperature. This study provides scientific evidence and insights into the adaptive management of the Changjiang Basin.

Microglia-induced autophagic death of neurons via IL-6/STAT3/miR-30d signaling following hypoxia/ischemia - Jun Shu; Xu-Hao Fang; Ya-Jian Li; Yao Deng; Wen-Shi Wei; Li Zhang (Molecular Biology Reports, 2022)

Development of Quercus acutissima (Fagaceae) pollen tubes inside pistils during the sexual reproduction process - Min Deng; Kaiping Yao; Chengcheng Shi; Wen Shao; Qiansheng Li (Planta, 2022)

Transcriptome Changes Induced by Botrytis cinerea Stress and Weighted Gene Co-expression Network Analysis (WGCNA) in Actinidia chinensis - Zhe-Xin Li; Wen-Lin Zhang; Deng-Wei Jue; Xia Liu; Yu-Song Jiang; Jian-Min Tang (Plant Molecular Biology Reporter, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Monascuslactams A–D, cytotoxic γ-lactams from marine fungus Monascus albidus BB3 - Qi Guo; Xiao-Ming Dai; Wen-Jian Lan; Liu-Ping Chen; Chi-Keung Lam; Gong-Kan Feng; Rong Deng; Xiao-Feng Zhu; Hou-Jin Li (Natural Product Research, 2022)

Xylariaopyrones E–I, five new α-pyrone derivatives from the endophytic fungus Xylariales sp. (HM-1) - Wen-Wen Yang; Li-Wen Lu; Xue-Qing Zhang; Shang-Song Bao; Fei Cao; Zhi-Yong Guo; Zhang-Shuang Deng; Peter Proksch (Natural Product Research, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Mass Transfer during Hematitization and Implications for Uranium Mineralization in the Zoujiashan Deposit, Xiangshan Volcanic Basin - Teng Deng; Guoxiang Chi; Xiongjie Zhang; Zenghua Li; Deru Xu; Shengmiao Li; Pengfei Du; Pei Shang; Shaohao Zou; Wanpeng Zhou; Ke Xu; Hai Yan; et al. (Journal of Earth Science, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Warming reshaped the microbial hierarchical interactions - Yuqi Zhou; Baoyu Sun; Baohua Xie; Kai Feng; Zhaojing Zhang; Zheng Zhang; Shuzhen Li; Xiongfeng Du; Qi Zhang; Songsong Gu; Wen Song; Linlin Wang; et al. (Global Change Biology, 2021)
Global warming may alter microbially mediated ecosystem functions through reshaping of microbial diversity and modified microbial interactions. Here, we examined the effects of 5‐year experimental warming on different microbial hierarchical groups in a coastal nontidal soil ecosystem, including prokaryotes (i.e., bacteria and archaea), fungi, and Cercozoa, which is a widespread phylum of protists. Warming significantly altered the diversity and structure of prokaryotic and fungal communities in soil and additionally decreased the complexity of the prokaryotic network and fragmented the cercozoan network. By using the Inter‐Domain Ecological Network approach, the cross‐trophic interactions among prokaryotes, fungi, and Cercozoa were further investigated. Under warming, cercozoan–prokaryotic and fungal–prokaryotic bipartite networks were simplified, whereas the cercozoan–fungal network became slightly more complex. Despite simplification of the fungal–prokaryotic network, the strengthened synergistic interactions between saprotrophic fungi and certain prokaryotic groups, such as the Bacteroidetes, retained these phyla within the network under warming. In addition, the interactions within the fungal community were quite stable under warming conditions, which stabilized the interactions between fungi and prokaryotes or protists. Additionally, we found the microbial hierarchical interactions were affected by environmental stress (i.e., salinity and pH) and soil nutrients. Interestingly, the relevant microbial groups could respond to different soil properties under ambient conditions, whereas under warming these two groups tended to respond to similar soil properties, suggesting network hub species responded to certain environmental changes related to warming, and then transferred this response to their partners through trophic interactions. Finally, warming strengthened the network modules’ negative association with soil organic matters through some fungal hub species, which might trigger soil carbon loss in this ecosystem. Our study provides new insights into the response and feedback of microbial hierarchical interactions under warming scenario.

Developing a two-step improved damage creep constitutive model based on soft rock saturation-loss cycle triaxial creep test - Anrun Li; Hui Deng; Haojie Zhang; Mingliang Jiang; Hanhan Liu; Yuyue Xiao; Jing Wen (Natural Hazards, 2021)

Paleoproterozoic S-type granites in the Lengshui complex, South China: Implications for the tectonic evolution of the Yangtze Block - Kuizhou Li; Qi Deng; Jian Wang; Chris Yakymchuk; Mingcai Hou; Xiaozhuang Cui; Guangming Ren; Fei Ren; Wen Luo (International Geology Review, 2021)

Geological controls of shale gas accumulation and enrichment mechanism in Lower Cambrian Niutitang Formation of western Hubei, Middle Yangtze, China - Lulu Xu; Saipeng Huang; Zaoxue Liu; Yaru Wen; Xianghui Zhou; Yanlin Zhang; Xiongwei Li; Deng Wang; Fan Luo; Cheng Chen (Frontiers of Earth Science, 2021)

Natural Climate Solutions for China: The Last Mile to Carbon Neutrality - Zhangcai Qin; Xi Deng; Bronson Griscom; Yao Huang; Tingting Li; Pete Smith; Wenping Yuan; Wen Zhang (Advances in Atmospheric Sciences, 2021)

Correction to: Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Exploring the Genetic Association of the ABAT Gene with Alzheimer’s Disease - Quanzhen Zheng; Rui Bi; Min Xu; Deng-Feng Zhang; Li-Wen Tan; Ya-Ping Lu; Yong-Gang Yao (Molecular Neurobiology, 2021)

Identification of a microalgae-yeast coculture system for nutrient removal in shrimp culture wastewater - Zhizhan Luo; Wen Huang; Chuntian Zheng; Ji Li; Long Yun; Huiming Sun; Guoxia Wang; Xiaoying Chen; Wenyan Mo; Dun Deng; Peng Luo; Huo Li; et al. (Journal of Applied Phycology, 2021)

The dynamics in rhizosphere microbial communities under bacterial wilt resistance by mulberry genotypes - Zhaoxia Dong; Yao Guo; Cui Yu; Zhu Zhixian; Mo Rongli; Wen Deng; Yong Li; Xingming Hu (Archives of Microbiology, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Astragaloside IV inhibits palmitic acid-induced apoptosis through regulation of calcium homeostasis in mice podocytes - Yingjun Zang; Shuang Liu; Aili Cao; Xiangyu Shan; Wenjuan Deng; Zhijun Li; Hao Wang; Yunman Wang; Li Wang; Wen Peng (Molecular Biology Reports, 2021)
Loss of podocytes is a hallmark of diabetic nephropathy, and a growing body of evidence indicates that podocytes are susceptible to palmitic acid (PA). We have previously shown that AS-IV inhibited PA-induced podocyte apoptosis by activating sarcoendoplasmic reticulum Ca 2+ ATPase (SERCA), which indicate calcium regulation may involve in the process. Immunofluorescence staining, Western blot and flow cytometry were used to measure the protective efficacy of AS-IV to ameliorate PA-induced ER stress and podocyte apoptosis. Meanwhile, AS-IV inhibited cytochrome c release, decreased mitochondrial membrane potential, accompany with the depletion of endoplasmic reticulum Ca 2+ and elevation of cytosolic and mitochondrial Ca 2+ . Sequestration of cytosolic calcium with BAPTA-AM limited the response of podocyte apoptosis, while during the process the effect of AS-IV was also restrained. In contrast, elevation of cytosolic calcium with calcium ionophore ionomycin was depressed by AS-IV addition. Furthermore, inhibiting TRPC6 expression with SKF96365 or TRPC6 siRNA counteracted the beneficial effect of AS-IV. Our study provides further evidence to conclude the inhibitory effect of AS-IV to podocyte apoptosis is Ca 2+ -dependent. And the efficacy correlates with inhibiting TRPC6-mediated Ca 2+ influx, and then cellular Ca 2+ disturbance was coordinated.

Simultaneously decreased temporal variability and enhanced variability-strength coupling of emotional network connectivities are related to positive symptoms in patients with schizophrenia - Yanjia Deng; Shuguang Han; Dongliang Cheng; Hui Li; Bin Zhang; Youyong Kong; Yong Lin; Yingjia Li; Ge Wen; Kai Liu (Brain Imaging and Behavior, 2021)

Assembly of Satsuma mandarin mitochondrial genome and identification of cytoplasmic male sterility–specific ORFs in a somatic cybrid of pummelo - Shuai Zhang; Zhao-Ping Yin; Xiao-Meng Wu; Chao-Chao Li; Kai-Dong Xie; Xiu-Xin Deng; Jude W. Grosser; Wen-Wu Guo (Tree Genetics & Genomes, 2020)

Factors associated with a SARS-CoV-2 recurrence after hospital discharge among patients with COVID-19: systematic review and meta-analysis - Meng-qi Yao; Qiu-xian Zheng; Jia Xu; Jing-wen Deng; Tian-tian Ge; Hai-bo Zhou; Feng-tian Wu; Xin-yu Gu; Qin Yang; Yan-li Ren; Gang Wang; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2020)

Metagenomics analysis of the effects of long-term stand age on beneficial soil bacterial community structure under Chinese ancient mulberry farming practice - Yu Cui; Li Yong; Mo Rongli; Deng Wen; Zhu Zhixian; Hu Xingming (Horticulture, Environment, and Biotechnology, 2020)

Sphingobacterium endophyticum sp. nov., a novel endophyte isolated from halophyte - Yang-Yang Liu; Fang Liu; Yu-Qian Li; Rui-Feng Lei; Qin Ma; Manik Prabhu Narsing Rao; Dilireba Abudourousuli; Zulihumaer Rouzi; Muyesaier Aosiman; Deng-Di An; Wen-Jun Li (Archives of Microbiology, 2020)

Environmental perspectives of microplastic pollution in the aquatic environment: a review - Manzoor Ahmad; Jia-Ling Li; Pan-Deng Wang; Wael N. Hozzein; Wen-Jun Li (Marine Life Science & Technology, 2020)

Overexpression of PREX1 in oral squamous cell carcinoma indicates poor prognosis - Shu-Cheng Wan; Hao Wu; Hao Li; Wei-Wei Deng; Yao Xiao; Cong-Cong Wu; Lei-Lei Yang; Wen-Feng Zhang; Zhi-Jun Sun (Journal of Molecular Histology, 2020)

Sodium Para-aminosalicylic Acid Reverses Changes of Glutamate Turnover in Manganese-Exposed Rats - Zhao-Cong Li; Fang Wang; Shao-Jun Li; Lin Zhao; Jun-Yan Li; Yue Deng; Xiao-Juan Zhu; Yu-Wen Zhang; Dong-Jie Peng; Yue-Ming Jiang (Biological Trace Element Research, 2020)

A histone deacetylase, GhHDT4D, is positively involved in cotton response to drought stress - Jing-Bo Zhang; Shao-Ping He; Jing-Wen Luo; Xin-Peng Wang; Deng-Di Li; Xue-Bao Li (Plant Molecular Biology, 2020)

Identification of pleiotropic genes between risk factors of stroke by multivariate metaCCA analysis - Zun Wang; Jonathan Greenbaum; Chuan Qiu; Kelvin Li; Qian Wang; Si-Yuan Tang; Hong-Wen Deng (Molecular Genetics and Genomics, 2020)

Early use of dexamethasone increases Nr4a1 in Kupffer cells ameliorating acute liver failure in mice in a glucocorticoid receptor-dependent manner - Jing-wen Deng; Qin Yang; Xiao-peng Cai; Jia-ming Zhou; Wei-gao E; Yan-dong An; Qiu-xian Zheng; Meng Hong; Yan-li Ren; Jun Guan; Gang Wang; Shu-jing Lai; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Vitamin D receptor gene methylation in patients with hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Hui-Ling Deng; Wen-Jun Wang; Mu-Qi Wang; Mei Li; Yu-Feng Zhang; Jun Wang; Shuang-Suo Dang (Archives of Virology, 2020)

Effects of long-term straw retention on soil microorganisms under a rice–wheat cropping system - Cui Yu; Yong Li; Rongli Mo; Wen Deng; Zhixian Zhu; Dongbi Liu; Xingming Hu (Archives of Microbiology, 2020)

Effects of crop straw biochars on aluminum species in soil solution as related with the growth and yield of canola (Brassica napus L.) in an acidic Ultisol under field condition - Wen-rui Zhao; Jiu-yu Li; Kai-ying Deng; Ren-yong Shi; Jun Jiang; Zhi-neng Hong; Wei Qian; Xian He; Ren-kou Xu (Environmental Science and Pollution Research, 2020)

Role of T-type Calcium Channels in Generating Hyperexcitatory Behaviors during Emergence from Sevoflurane Anesthesia in Neonatal Rats - Feng-Yan Shen; Byung-Gun Lim; Wen Wen; Yu Zhang; Bo Cao; Yue-Guang Si; Li-Qing Ma; Meng Deng; Yang In Kim; Young-Beom Kim; Ying-Wei Wang (Neuroscience Bulletin, 2020)

Identification of novel functional CpG-SNPs associated with type 2 diabetes and coronary artery disease - Zun Wang; Chuan Qiu; Xu Lin; Lan-Juan Zhao; Yong Liu; Xinrui Wu; Qian Wang; Wei Liu; Kelvin Li; Hong-Wen Deng; Si-Yuan Tang; Hui Shen (Molecular Genetics and Genomics, 2020)

Dryland agricultural environment and sustainable productivity - Gou-Xia Li; Bing-Cheng Xu; Li-Na Yin; Shi-Wen Wang; Sui-Qi Zhang; Lun Shan; Sang-Soo Kwak; Qingbo Ke; Xi-Ping Deng (Plant Biotechnology Reports, 2020)

Contrasting soil fungal communities at different habitats in a revegetated copper mine wasteland - Jie-liang Liang; Jun Liu; Tao-tao Yang; Pan-deng Wang; Sheng-chang Zhang; Pu Jia; Bin Liao; Wen-sheng Shu; Jin-tian Li (Soil Ecology Letters, 2020)

A recombinant infectious bronchitis virus from a chicken with a spike gene closely related to that of a turkey coronavirus - Yan Wang; Xuejiao Cui; Xu Chen; Shixing Yang; Yu Ling; Qianben Song; Su Zhu; Luying Sun; Chuang Li; Yu Li; Xutao Deng; Eric Delwart; et al. (Archives of Virology, 2020)

Cloning and characterization of a glycosyltransferase from Catharanthus roseus for glycosylation of cardiotonic steroids and phenolic compounds - Chao Wen; Wei Huang; Miao-Miao He; Wen-Li Deng; Hai-Hong Yu (Biotechnology Letters, 2020)

Lysobacter oculi sp. nov., isolated from human Meibomian gland secretions - Hua Bai; Huibin Lv; Aihua Deng; Xiaodan Jiang; Xuemin Li; Tingyi Wen (Antonie van Leeuwenhoek, 2020)

One bis-indole alkaloid-voacamine from Voacanga africana Stapf: biological activity evaluation of PTP1B in vitro utilizing enzymology method based on SPRi expriment - Yan-Qiu Wang; Hong-Xiang Li; Xiao-Chun Liu; Jin-Shuang Zhao; Rong-Qiang Liu; Wen-ying Huai; Wei-Jun Ding; Tian-E Zhang; Yun Deng (Natural Product Research, 2019)

Relevance of number and physiological status of conspecifics in preventing stress-induced decreases in newly proliferated cells and neuroblasts - Li-Han Sun; Wen-Yu Tzeng; Yi-Han Liao; Wen-Ting Deng; Chianfang G. Cherng; Lung Yu (Psychopharmacology, 2019)

Detection and attribution of upper-tropospheric warming over the tropical western Pacific - Yana Li; Song Yang; Yi Deng; Xiaoming Hu; Ming Cai; Wen Zhou (Climate Dynamics, 2019)

Methane emissions responding to Azolla inoculation combined with midseason aeration and N fertilization in a double-rice cropping system - Ya-Dong Yang; He-Shui Xu; Deng-Yun Li; Jing-Na Liu; Jiang-Wen Nie; Zhao-Hai Zeng (Environmental Science and Pollution Research, 2019)

Antifungal Susceptibility Profile of Candida Albicans Isolated from Vulvovaginal Candidiasis in Xinjiang Province of China - Liang Yan; Xiao-dong Wang; Seyedmojtaba Seyedmousavi; Juan-na Yuan; Palida Abulize; Wei-hua Pan; Nong Yu; Ya-li Yang; Hai-qing Hu; Wan-qing Liao; Shu-wen Deng (Mycopathologia, 2019)

Viral metagenomics reveals significant viruses in the genital tract of apparently healthy dairy cows - Yu Ling; Xiaodan Zhang; Guilan Qi; Shixing Yang; Li Jingjiao; Quan Shen; Xiaochun Wang; Li Cui; Xiuguo Hua; Xutao Deng; Eric Delwart; Wen Zhang (Archives of Virology, 2019)

Asian black bear (Ursus thibetanus) picornavirus related to seal aquamavirus A - Haoning Wang; Wen Zhang; Shixiing Yang; Ning Kong; Hai Yu; Hao Zheng; Fei Gao; Wu Tong; Liwei Li; Xiaolong Wang; Xutao Deng; Eric Delwart; et al. (Archives of Virology, 2019)

The fecal virome of red-crowned cranes - Yan Wang; Shixing Yang; Dawei Liu; Chenglin Zhou; Wang Li; Yuan Lin; Xiaochun Wang; Quan Shen; Hua Wang; Chuang Li; Minghui Zong; Yuzhu Ding; et al. (Archives of Virology, 2019)

Ethical considerations of cellular immunotherapy for cancer - Sang-sang Ren; Jing-wen Deng; Meng Hong; Yan-li Ren; Hai-jing Fu; Yan-ning Liu; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Serum Oxidative Stress Marker Levels in Unmedicated and Medicated Patients with Schizophrenia - Zhi-Le Bai; Xue-Song Li; Guang-Yang Chen; Yang Du; Ze-Xu Wei; Xi Chen; Guang-En Zheng; Wen Deng; Yong Cheng (Journal of Molecular Neuroscience, 2018)

Antibiotic distribution, risk assessment, and microbial diversity in river water and sediment in Hong Kong - Wen-Jing Deng; Na Li; Guang-Guo Ying (Environmental Geochemistry and Health, 2018)

Over-expression of IQGAP1 indicates poor prognosis in head and neck squamous cell carcinoma - Cong-Cong Wu; Hao Li; Yao Xiao; Lei-Lei Yang; Lei Chen; Wei-Wei Deng; Lei Wu; Wen-Feng Zhang; Zhi-Jun Sun (Journal of Molecular Histology, 2018)

Synergistic effects and related bioactive mechanisms of Potentilla fruticosa Linn. leaves combined with green tea polyphenols studied with microbial test system (MTS) - Ze-Hua Liu; Zi-Wen Luo; Deng-Wu Li; Dong-Mei Wang; Xia Ji (Natural Product Research, 2018)

Inhibition of KLF7-Targeting MicroRNA 146b Promotes Sciatic Nerve Regeneration - Wen-Yuan Li; Wei-Ting Zhang; Yong-Xia Cheng; Yan-Cui Liu; Feng-Guo Zhai; Ping Sun; Hui-Ting Li; Ling-Xiao Deng; Xiao-Feng Zhu; Ying Wang (Neuroscience Bulletin, 2018)

Identifying potentially common genes between dyslipidemia and osteoporosis using novel analytical approaches - Xu Lin; Cheng Peng; Jonathan Greenbaum; Zhang-Fang Li; Ke-Hao Wu; Zeng-Xin Ao; Tong Zhang; Jie Shen; Hong-Wen Deng (Molecular Genetics and Genomics, 2018)

Occurrence and health risk assessment of organotins in waterworks and the source water of the Three Gorges Reservoir Region, China - Ting Deng; Lei Wu; Jun-Min Gao; Bin Zhou; Ya-Li Zhang; Wen-Nan Wu; Zhuo-Heng Tang; Wen-Chao Jiang; Wei-Lin Huang (Environmental Science and Pollution Research, 2018)

Unexpected fungal communities in the Rehai thermal springs of Tengchong influenced by abiotic factors - Kai-Hui Liu; Xiao-Wei Ding; Nimaichand Salam; Bo Zhang; Xiao-Fei Tang; Baiwan Deng; Wen-Jun Li (Extremophiles, 2018)

Association of IL-28B, TBX21 gene polymorphisms and predictors of virological response for chronic hepatitis C - Dan Yan Zhu; Xiao Zhao Deng; Yu Meng Zhu; Guo Tao Li; Guo Qiang Zhang; Ling Ju Wang; Jing Hai Zhang; Wen Xiao; Zhen Xian Zhou; Wei Liang Ding (Archives of Virology, 2018)

Production of Humic Acid by a Bacillus megaterium Strain Using Vinasse - Nan Li; Zhi-Nian Deng; Yuan-Wen Wei; Hui-Qing Cao; Yang-Rui Li (Sugar Tech, 2018)

ELMOD3, a novel causative gene, associated with human autosomal dominant nonsyndromic and progressive hearing loss - Wu Li; Jie Sun; Jie Ling; Jiada Li; Chufeng He; Yalan Liu; Hongsheng Chen; Meichao Men; Zhijie Niu; Yuyuan Deng; Meng Li; Taoxi Li; et al. (Human Genetics, 2018)

A Semi-analytical Model for Pressure-Dependent Permeability of Tight Sandstone Reservoirs - Su-Yang Zhu; Zhi-Min Du; Chuan-Liang Li; Alireza Salmachi; Xiao-Long Peng; Chao-Wen Wang; Ping Yue; Peng Deng (Transport in Porous Media, 2018)

Intramuscular Delivery of scAAV9-hIGF1 Prolongs Survival in the hSOD1G93A ALS Mouse Model via Upregulation of D-Amino Acid Oxidase - HuiQian Lin; HaoJie Hu; WeiSong Duan; YaLing Liu; GuoJun Tan; ZhongYao Li; YaKun Liu; BinBin Deng; XueQin Song; Wan Wang; Di Wen; Ying Wang; et al. (Molecular Neurobiology, 2018)

Phylogenetic and genetic characterization of a 2017 clinical isolate of H7N9 virus in Guangzhou, China during the fifth epidemic wave - Yongqiang Deng; Chunlin Li; Jianfeng Han; Yingfen Wen; Jian Wang; Wenxing Hong; Xiaofeng Li; Zhongyu Liu; Qing Ye; Jing Li; Changshuai Zhou; Lei Yu; et al. (Science China Life Sciences, 2017)

The complete mitochondrial genome of a threatened loach (Beaufortia kweichowensis) and its phylogeny - Zheng-Yong Wen; Bi-Wen Xie; Chuan-Jie Qin; Jun Wang; Deng-Yue Yuan; Rui Li; Yuan-Chao Zou (Conservation Genetics Resources, 2017)

Identification of a novel reassortant A (H9N6) virus in live poultry markets in Poyang Lake region, China - Heng Zhang; Mingbin Liu; Xiaoxu Zeng; Xiang Zhao; Zhiqiang Deng; Lei Yang; Wenbing Chen; Zi Li; Ming Jiao; Wen Xia; Bin Han; Haiying Chen; et al. (Archives of Virology, 2017)

Erratum to: Disruption of mindin exacerbates cardiac hypertrophy and fibrosis - Zhou-Yan Bian; Xiang Wei; Shan Deng; Qi-Zhu Tang; Jinghua Feng; Yan Zhang; Chen Liu; Ding-Sheng Jiang; Ling Yan; Lian-Feng Zhang; Manyin Chen; John Fassett; et al. (Journal of Molecular Medicine, 2017)

Predicting posttraumatic hydrocephalus: derivation and validation of a risk scoring system based on clinical characteristics - Hao Chen; Fang Yuan; Shi-Wen Chen; Yan Guo; Gan Wang; Zhi-Feng Deng; Heng-Li Tian (Metabolic Brain Disease, 2017)

Comparison of infrared canopy temperature in a rubber plantation and tropical rain forest - Qing-Hai Song; Yun Deng; Yi -Ping Zhang; Xiao-Bao Deng; You-Xing Lin; Li-Guo Zhou; Xue-Hai Fei; Li-Qing Sha; Yun-Tong Liu; Wen-Jun Zhou; Jin-Bo Gao (International Journal of Biometeorology, 2017)

Geochronology and geochemistry of volcanic rocks in the Arbasay Formation, Xinjiang Province (Northwest China): implications for the tectonic evolution of the North Tianshan - Jialin Wang; Chaodong Wu; Zhuang Li; Wen Zhu; Yiwen Chen; Qingyun Li; Jun Wu; Langjiang Deng; Rong Chen (International Geology Review, 2017)

The complete mitochondrial genome of a threatened loach (Sinibotia reevesae) and its phylogeny - Yuan-Chao Zou; Bi-Wen Xie; Chuan-Jie Qin; Yong-Ming Wang; Deng-Yue Yuan; Rui Li; Zheng-Yong Wen (Genes & Genomics, 2017)

Densoviruses in oyster Crassostrea ariakensis - Yan-Jun Kang; Wei Huang; A-li Zhao; Dan-Dan Lai; Lin Shao; Yan-Qin Shen; Xutao Deng; Eric Delwart; Wen Zhang (Archives of Virology, 2017)

Blockade of Notch signaling promotes acetaminophen-induced liver injury - Longfeng Jiang; Michael Ke; Shi Yue; Wen Xiao; Youde Yan; Xiaozhao Deng; Qi-Long Ying; Jun Li; Bibo Ke (Immunologic Research, 2017)

Repellence of the main components from the essential oil of Glycosmis lucida Wall. ex Huang against two stored product insects - Shan-Shan Guo; Wen-Juan Zhang; Kai Yang; Jun-Yu Liang; Chun-Xue You; Cheng-Fang Wang; Yin-Ping Li; Zhu-Feng Geng; Zhi-Wei Deng; Shu-Shan Du (Natural Product Research, 2017)

A Point Mutation in SCN1A 5′ Genomic Region Decreases the Promoter Activity and Is Associated with Mild Epilepsy and Seizure Aggravation Induced by Antiepileptic Drug - Qu-Wen Gao; Li-Dong Hua; Jie Wang; Cui-Xia Fan; Wei-Yi Deng; Bin Li; Wen-Jun Bian; Chuan-Xing Shao; Na He; Peng Zhou; Wei-Ping Liao; Yi-Wu Shi (Molecular Neurobiology, 2017)

Pilot Demonstration of Ceramic Membrane Ultrafiltration of Sugarcane Juice for Raw Sugar Production - Wen Li; Guo-Qing Ling; Chang-Rong Shi; Kai Li; Hai-Qin Lu; Fang-Xue Hang; Yu Zhang; Cai-Feng Xie; Deng-Jun Lu; Hong Li (Sugar Tech, 2017)

Glucocorticoids Prevent Enterovirus 71 Capsid Protein VP1 Induced Calreticulin Surface Exposure by Alleviating Neuronal ER Stress - Dan-Dan Hu; Jian-Ning Mai; Li-Ya He; Pei-Qing Li; Wen-Xiong Chen; Jian-Jiang Yan; Wei-Dong Zhu; Li Deng; Dan Wei; Di-Hui Liu; Si-Da Yang; Zhi-Bin Yao (Neurotoxicity Research, 2017)

Transcriptional and Epigenetic Regulation in Injury-Mediated Neuronal Dendritic Plasticity - Ying Wang; Wen-Yuan Li; Zhi-Gang Li; Li-Xin Guan; Ling-Xiao Deng (Neuroscience Bulletin, 2017)

MCP1 triggers monocyte dysfunctions during abnormal osteogenic differentiation of mesenchymal stem cells in ankylosing spondylitis - Zhongyu Xie; Peng Wang; Jinteng Li; Yuxi Li; Shan Wang; Xiaohua Wu; Suhe Sun; Shuizhong Cen; Hongjun Su; Wen Deng; Zhenhua Liu; Yi Ouyang; et al. (Journal of Molecular Medicine, 2017)

A novel bocavirus from domestic mink, China - Shixing Yang; Yan Wang; Wang Li; Zhaobin Fan; Lili Jiang; Yuan Lin; Xingli Fu; Quan Shen; Zixuan Sun; Xiaochun Wang; Xutao Deng; Wen Zhang; et al. (Virus Genes, 2016)

Oral administration of Schisandra chinensis extract suppresses Dnmt1 expression in Kunming mice ovaries - Feng-Rui Wu; Deng-kun Li; Mi-mi Su; Yong Liu; Biao Ding; Rong Wang; Wen-yong Li (Genes & Genomics, 2016)

NF-κB is involved in the LPS-mediated proliferation and apoptosis of MAC-T epithelial cells as part of the subacute ruminal acidosis response in cows - Wen-Jie Fan; He-Ping Li; He-Shui Zhu; Shi-Ping Sui; Pei-Ge Chen; Yue Deng; Tong-Ming Sui; Yue-Ying Wang (Biotechnology Letters, 2016)

Identification and molecular characterization of one novel 1SPl-encoded s-type low molecular weight glutenin B-subunit from 1Sl(1B) substitution line of wheat variety Chinese Spring (Triticum aestivum) - Xiong Deng; Shun-li Wang; Shou-min Zhen; Wen-ying Zhang; Yue-ming Yan (Biologia, 2016)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

Streptomyces xinjiangensis sp. nov., an actinomycete isolated from Lop Nur region - Cong Cheng; Yu-Qian Li; Mipeshwaree Devi Asem; Chun-Yan Lu; Xiao-Han Shi; Xiao Chu; Wan-Qin Zhang; Deng- Di An; Wen-Jun Li (Archives of Microbiology, 2016)

Inhibition of Adhesion of Enteropathogenic Escherichia coli to HEp-2 Cells by Binding of a Novel Peptide to EspB Protein - Duoyun Li; Zhong Chen; Hang Cheng; Jin-xin Zheng; Wei-guang Pan; Wei-zhi Yang; Zhi-jian Yu; Qi-wen Deng (Current Microbiology, 2016)

PD-1/PD-L1 signal pathway participates in HCV F protein-induced T cell dysfunction in chronic HCV infection - Wen Xiao; Long Feng Jiang; Xiao Zhao Deng; Dan Yan Zhu; Jia Ping Pei; Mao Lei Xu; Bing Jun Li; Chang Jun Wang; Jing Hai Zhang; Qi Zhang; Zhen Xian Zhou; Wei Liang Ding; et al. (Immunologic Research, 2016)

Bufavirus Protoparvovirus in feces of wild rats in China - Shixing Yang; Dawei Liu; Yan Wang; Fanyong Qu; Yilin He; Zixuan Sun; Quan Shen; Wang Li; Xingli Fu; Xutao Deng; Wen Zhang; Eric Delwart (Virus Genes, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

Recovery and characterization of homozygous lines from two sweet orange cultivars via anther culture - Shu-Ming Wang; Hong Lan; Hong-Bo Cao; Qiang Xu; Chun-Li Chen; Xiu-Xin Deng; Wen-Wu Guo (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

An artificially constructed Syngonium podophyllum-Aspergillus niger combinate system for removal of uranium from wastewater - Jia-dong He; Yong-dong Wang; Nan Hu; Dexin Ding; Jing Sun; Qin-wen Deng; Chang-wu Li; Fei Xu (Environmental Science and Pollution Research, 2015)

Nontuberculous mycobacterial osteomyelitis - Sheng Bi; Fei-Shu Hu; Hai-Ying Yu; Kai-Jin Xu; Bei-Wen Zheng; Zhong-Kang Ji; Jun-Jie Li; Mei Deng; Hai-Yang Hu; Ji-Fang Sheng (Infectious Diseases, 2015)

Saccharothrix lopnurensis sp. nov., a filamentous actinomycete isolated from sediment of Lop Nur - Yu-Qian Li; Lan Liu; Cong Cheng; Xiao-Han Shi; Chun-Yan Lu; Zhou-Yan Dong; Nimaichand Salam; Deng-Di An; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Effects of light intensity on the susceptibility of Nicotiana tabacum to cucumber mosaic virus - Li-Juan Chen; Han Ren; Xing-Guang Deng; Ya-Nan Li; Wen-Qiong Cha; Hong-Hui Lin; De-Hui Xi (Journal of General Plant Pathology, 2015)

Foxl2 of the Hong Kong catfish (Clarias fuscus): cDNA cloning, tissue distribution and changes in gene expression towards methyltestosterone, estradiol and letrozole exposure of the fries during gonadal differentiation - Si-ping Deng; Chun-hua Zhu; Jing Sun; Wen-da Wang; Tian-li Wu; Hua-pu Chen; Shang-li Shi; Guang-li Li (Genes & Genomics, 2015)

A gyrovirus infecting a sea bird - Linlin Li; Patricia A. Pesavento; Anne M. Gaynor; Rebecca S. Duerr; Tung Gia Phan; Wen Zhang; Xutao Deng; Eric Delwart (Archives of Virology, 2015)

Galactose supplementation enhance sialylation of recombinant Fc-fusion protein in CHO cell: an insight into the role of galactosylation in sialylation - Jintao Liu; Jie Wang; Li Fan; Xinning Chen; Dongdong Hu; Xiancun Deng; H. Fai Poon; Haibin Wang; Xuping Liu; Wen-Song Tan (World Journal of Microbiology and Biotechnology, 2015)

Monitoring sialylation levels of Fc-fusion protein using size-exclusion chromatography as a process analytical technology tool - Jintao Liu; Xinning Chen; Li Fan; Xiancun Deng; H. Fai Poon; Wen-Song Tan; Xuping Liu (Biotechnology Letters, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

Promotion of expression of interferon-stimulated genes in U937 monocytic cells by HIV RNAs, measured using stable isotope labeling with amino acids in cell culture (SILAC) - Yulan Li; Bin Wen; Ran Chen; Feng Jiang; Xiaofang Zhao; Xin Deng (Archives of Virology, 2015)

Common variants of the PINK1 and PARL genes do not confer genetic susceptibility to schizophrenia in Han Chinese - Xiao Li; Wen Zhang; Chen Zhang; Zhenghui Yi; Deng-Feng Zhang; Wei Gong; Jinsong Tang; Dong Wang; Weihong Lu; Xiaogang Chen; Yiru Fang; Yong-Gang Yao (Molecular Genetics and Genomics, 2015)

Conjugated linoleic acid alters growth performance, tissue lipid deposition, and fatty acid composition of darkbarbel catfish (Pelteobagrus vachelli) - Gui-Fang Dong; Wen-Zuo Liu; Lin-Zhou Wu; Deng-hang Yu; Feng Huang; Peng-Cheng Li; Yan-ou Yang (Fish Physiology and Biochemistry, 2015)

Arabidopsis drought-induced protein Di19-3 participates in plant response to drought and high salinity stresses - Li-Xia Qin; Yang Li; Deng-Di Li; Wen-Liang Xu; Yong Zheng; Xue-Bao Li (Plant Molecular Biology, 2014)

One new alkaloid from Chelidonium majus L. - Wen-Juan Zhang; Chun-Xue You; Cheng-Fang Wang; Li Fan; Ying Wang; Yang Su; Zhi-Wei Deng; Shu-Shan Du (Natural Product Research, 2014)

Isolation and characterization of LEAFY COTYLEDON 1-LIKE gene related to embryogenic competence in Citrus sinensis - Shi-ping Zhu; Jun Wang; Jun-li Ye; An-Dan Zhu; Wen-wu Guo; Xiu-xin Deng (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Ecto-Mesenchymal Stem Cells from Facial Process: Potential for Muscle Regeneration - Xin Nie; Yongjun Xing; Manjin Deng; Li Gang; Rui Liu; Yongjie Zhang; Xiujie Wen (Cell Biochemistry and Biophysics, 2014)

Cotton TCTP1 gene encoding a translationally controlled tumor protein participates in plant response and tolerance to aphids - Jian-Min Zhang; Liu-Feng Ma; Wen Li; Jie Zhang; Deng-Di Li; Xue-Bao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Photosynthetic activity and efficiency of Bothriochloa ischaemum and Lespedeza davurica in mixtures across growth periods under water stress - Wei-Zhou Xu; Xi-Ping Deng; Bing-Cheng Xu; Zhi-Juan Gao; Wen-Li Ding (Acta Physiologiae Plantarum, 2014)

Synthesis and cytotoxic activity of novel hybrid compounds between 2-alkylbenzofuran and imidazole - Wei-Chao Wan; Wen Chen; Lan-Xiang Liu; Yan Li; Li-Juan Yang; Xiao-Yan Deng; Hong-Bin Zhang; Xiao-Dong Yang (Medicinal Chemistry Research, 2014)

Molecular cloning, genomic structure, polymorphism and expression analysis of major histocompatibility complex class IIA gene of swamp eel Monopterus albus - Wei Li; Wen-xiu Sun; Liang Meng; Deng-wei Hong (Biologia, 2014)

Production and molecular characterization of diploid and tetraploid somatic cybrid plants between male sterile Satsuma mandarin and seedy sweet orange cultivars - Shi-Xin Xiao; Manosh Kumar Biswas; Meng-Ya Li; Xiu-Xin Deng; Qiang Xu; Wen-Wu Guo (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Characterization and cross-species amplification of 11 polymorphic microsatellite loci in Liobagrus marginatoides - Xiang-Yang Jia; Ying-Wen Li; Deng-Qiang Wang; Hui-Wu Tian; Bin Tu; Da-Qing Chen (Conservation Genetics Resources, 2013)

Assessing the impact of hydroelectric project construction on the ecological integrity of the Nuozhadu Nature Reserve, southwest China - Shiliang Liu; Qinghe Zhao; Minxia Wen; Li Deng; Shikui Dong; Cong Wang (Stochastic Environmental Research and Risk Assessment, 2013)

Changes in photosynthesis, chlorophyll fluorescence, and antioxidant enzymes of mulberry (Morus ssp.) in response to salinity and high-temperature stress - Cui Yu; Shujun Huang; Xingming Hu; Wen Deng; Chao Xiong; Chuhua Ye; Yong Li; Bo Peng (Biologia, 2013)

Protective Effects of Mangiferin in Subchronic Developmental Lead-Exposed Rats - Hao-Wen Li; Jia-Gang Deng; Zheng-Cai Du; Mao-Sheng Yan; Zhi-Xiang Long; Phuong-Thao Pham Thi; Ke-Di Yang (Biological Trace Element Research, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

Comparative transcriptome analysis of tobacco (Nicotiana tabacum) leaves to identify aroma compound-related genes expressed in different cultivated regions - Bo Lei; Xue-Hua Zhao; Kai Zhang; Jie Zhang; Wei Ren; Zhu Ren; Yi Chen; Hui-Na Zhao; Wen-Jie Pan; Wei Chen; Hong-Xun Li; Wen-Ya Deng; et al. (Molecular Biology Reports, 2013)

Functionalized single-walled carbon nanotubes cause reversible acute lung injury and induce fibrosis in mice - Yanli Zhang; Jiejie Deng; Yanxu Zhang; Feng Guo; Chenggang Li; Zhen Zou; Wen Xi; Jun Tang; Yang Sun; Peng Yang; Zongsheng Han; Dangsheng Li; et al. (Journal of Molecular Medicine, 2013)

Transcriptional profiling of genes involved in embryogenic, non-embryogenic calluses and somatic embryogenesis of Valencia sweet orange by SSH-based microarray - Xiao-Xia Ge; Li-Jun Chai; Zheng Liu; Xiao-Meng Wu; Xiu-Xin Deng; Wen-Wu Guo (Planta, 2012)

Construction of EGFP-Labeling System for Visualizing the Infection Process of Xanthomonas axonopodis pv. citri in planta - Li-Ping Liu; Zi-Niu Deng; Jin-Wang Qu; Jia-Wen Yan; Vittoria Catara; Da-Zhi Li; Gui-You Long; Na Li (Current Microbiology, 2012)

Disruption of mindin exacerbates cardiac hypertrophy and fibrosis - Zhou-Yan Bian; Xiang Wei; Shan Deng; Qi-Zhu Tang; Jinghua Feng; Yan Zhang; Chen Liu; Ding-Sheng Jiang; Ling Yan; Lian-Feng Zhang; Manyin Chen; John Fassett; et al. (Journal of Molecular Medicine, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

C/EBP-α ameliorates CCl4-induced liver fibrosis in mice through promoting apoptosis of hepatic stellate cells with little apoptotic effect on hepatocytes in vitro and in vivo - Li-Li Tao; Yuan-Yuan Cheng; Di Ding; Shuang Mei; Jia-Wen Xu; Juan Yu; Qi Ou-Yang; Long Deng; Qi Chen; Qing-Quan Li; Zu-De Xu; Xiu-Ping Liu (Apoptosis, 2012)

Genome-wide association study identifies HMGN3 locus for spine bone size variation in Chinese - Shu-Feng Lei; Hui Shen; Tie-Lin Yang; Yan Guo; Shan-Shan Dong; Xiang-Hong Xu; Fei-Yan Deng; Qing Tian; Yong-Jun Liu; Yao-Zhong Liu; Jian Li; Hong-Wen Deng (Human Genetics, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Molecular genetic studies of gene identification for sarcopenia - Li-Jun Tan; Shan-Lin Liu; Shu-Feng Lei; Christopher J. Papasian; Hong-Wen Deng (Human Genetics, 2012)

Overexpression of the trehalose-6-phosphate synthase gene OsTPS1 enhances abiotic stress tolerance in rice - Hao-Wen Li; Bai-Sheng Zang; Xing-Wang Deng; Xi-Ping Wang (Planta, 2011)

Identification of an alternative splicing isoform of chicken Lmbr1 - Yanqun Huang; Wen Chen; Ning Li; Xuemei Deng; Xiangtao Kang; Xiaojun Liu (Molecular Biology Reports, 2011)

Analysis of the fungi community in multiple- and single-grains Zaopei from a Luzhou-flavor liquor distillery in western China - Si Shi; Lei Zhang; Zheng-yun Wu; Wen-xue Zhang; Yu Deng; Fang-da Zhong; Jia-min Li (World Journal of Microbiology and Biotechnology, 2011)

De novo engineering and metabolic flux analysis of inosine biosynthesis in Bacillus subtilis - Haojian Li; Guoqiang Zhang; Aihua Deng; Ning Chen; Tingyi Wen (Biotechnology Letters, 2011)

Transgenic sugarcane plants expressing high levels of modified cry1Ac provide effective control against stem borers in field trials - Li-Xing Weng; Hai-Hua Deng; Jin-Ling Xu; Qi Li; Yu-Qian Zhang; Zi-De Jiang; Qi-Wei Li; Jian-Wen Chen; Lian-Hui Zhang (Transgenic Research, 2011)

Viral distribution and lesions in Kunming mice experimentally infected with porcine circovirus type 2b - Zhi-Bang Deng; Nai-Dong Wang; Dao-Jun Xu; An-Wen Yuan; Meng Ge; Wei Luo; Li-Qun Xue; Xing-Long Yu (Veterinary Research Communications, 2011)

Phenotypic and Genotypic Characterization Vibrio cholerae O139 of Clinical and Aquatic Isolates in China - Bai-sheng Li; Hai-ling Tan; Duo-chun Wang; Xiao-ling Deng; Jing-diao Chen; Hao-jie Zhong; Bi-xia Ke; Chang-wen Ke; Biao Kan (Current Microbiology, 2011)

The effect of excess expression of GFP in a novel heart-specific green fluorescence zebrafish regulated by nppa enhancer at early embryonic development - Wen Huang; Yun Deng; Wei Dong; Wuzhou Yuan; Yongqi Wan; Xiaoyan Mo; Yongqing Li; Zequn Wang; Yuequn Wang; Karen Ocorr; Bo Zhang; Shuo Lin; et al. (Molecular Biology Reports, 2011)

A new cytotoxic iridoid from Callicarpa nudiflora - Wen-Li Mei; Zhuang Han; Hai-Bin Cui; You-Xing Zhao; Yuan-Yuan Deng; Hao-Fu Dai (Natural Product Research, 2010)

Molecular characterization, expression profile and association analysis with carcass traits of porcine LCAT gene - Mu Qiao; Hua-Yu Wu; Feng-E Li; Si-Wen Jiang; Yuan-Zhu Xiong; Chang-Yan Deng (Molecular Biology Reports, 2010)

Effect of dietary protein reduction with synthetic amino acids supplementation on growth performance, digestibility, and body composition of juvenile Pacific white shrimp, Litopenaeus vannamei - Ming-Yan Huai; Yong-Jian Liu; Li-Xia Tian; Shi-Xi Deng; An-Long Xu; Wen Gao; Hui-Jun Yang (Aquaculture International, 2010)

Inhibition of lung metastasis in mice by intravascular injection of dendritic cells and natural killer cells - Hui-fang Lv; Feng Cui; Chang-hua Yu; Li-li Deng; Jing-jing Ji; Dan Lu; Yu Yang; Wen-xiu Wang; Yu-qing Xu (Biotechnology Letters, 2009)

Anthraquinone derivatives from Micromonospora rhodorangea - Chun-Mei Xue; Li Tian; Wen-Han Lin; Zhi-Wei Deng (Natural Product Research, 2009)

Silkworm powder containing manganese superoxide dismutase regulated the immunity and inhibited the growth of Hepatoma 22 cell in mice - Wan-Fu Yue; Wen Deng; Xing-Hua Li; Bhaskar Roy; Guang-Li Li; Jian-Mei Liu; Xiao-Feng Wu; Hong-Xiang Sun; Min-Li Yao; Wan Chi Cheong David; Yun-Gen Miao (Molecular Biology Reports, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Manganese superoxide dismutase expressed in silkworm larvae, Bombyx mori L enhances the NK activity and splenocyte proliferation against Sarcoma 180 tumor cells in vivo - Wan-Fu Yue; Min-Li Yao; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Wen Deng; Hong-Xiang Sun; Ji-Yong Zhou; Chuan-Xi Zhang; Yun-Gen Miao (Molecular Biology Reports, 2009)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Evidence of Gene Conversion in the Evolutionary Process of the Codon 41/42 (-CTTT) Mutation Causing β-Thalassemia in Southern China - Wen Zhang; Wang-Wei Cai; Wei-Ping Zhou; Hai-Peng Li; Liang Li; Wei Yan; Qin-Kai Deng; Ya-Ping Zhang; Yun-Xin Fu; Xiang-Min Xu (Journal of Molecular Evolution, 2008)

Fusion insect-resistant gene mediated by matrix attachment region (MAR) sequence in transgenic sugarcane - Zhi-Nian Deng; Yuan-Wen Wei; Wei-Li Lü; Yang-Rui Li (Sugar Tech, 2008)

ZNF418, a novel human KRAB/C2H2 zinc finger protein, suppresses MAPK signaling pathway - Yongqing Li; Dan Yang; Yan Bai; Xiaoyang Mo; Wen Huang; Wuzhou Yuan; Zhaochu Yin; Yun Deng; Oleg Murashko; Yuequn Wang; Xiongwei Fan; Chuanbing Zhu; et al. (Molecular and Cellular Biochemistry, 2008)

Association study of the oestrogen signalling pathway genes in relation to age at natural menopause - Li-Na He; Dong-Hai Xiong; Yong-Jun Liu; Feng Zhang; Robert R. Recker; Hong-Wen Deng (Journal of Genetics, 2007)

Characterization and identification of the candidate gene of rice thermo-sensitive genic male sterile gene tms5 by mapping - Qingkai Yang; Chunyang Liang; Wen Zhuang; Jun Li; Huabing Deng; Qiyun Deng; Bin Wang (Planta, 2006)

Differential Gene Expression in Sugarcane Regulated by Ethephon at Early Growth Stage - Yuan-Wen Wei; Chun-Jin Hu; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2006)

Genetic linkage of human height is confirmed to 9q22 and Xq24 - Yao-Zhong Liu; Peng Xiao; Yan-fang Guo; Dong-Hai Xiong; Lan-Juan Zhao; Hui Shen; Yong-Jun Liu; Volodymyr Dvornyk; Ji-Rong Long; Hong-Yi Deng; Jin-Long Li; Robert R. Recker; et al. (Human Genetics, 2006)

Association tests of interleukin-6 (IL-6) and type II tumor necrosis factor receptor (TNFR2) genes with bone mineral density in Caucasians using a re-sampling approach - Peng Xiao; Peng-Yuan Liu; Yan Lu; Yan-Fang Guo; Dong-Hai Xiong; Li-Hua Li; Robert R. Recker; Hong-Wen Deng (Human Genetics, 2005)

Erratum: Involvement of capsaicin-sensitive sensory nerves in early and delayed cardioprotection induced by a brief ischaemia of the small intestine - Yuan-Jian Li; Zi-Lue Tang; Wen Dai; Han-Wu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 1999)

The effect of lanthanide chloride on abscisic acid and electron-transport activity of some crops - Fu Li Zeng; Ming Feng Zhang; Shao Min Zhou; Ji Gui Wu; Ru Wen Deng (Biological Trace Element Research, 1999)